Cooperative management reshapes seasonal nitrogen synchrony and surface-water nitrogen risk in pastoral regions - Tianyun Qi; Tianer Song; Mei Huang; Wenyin Wang; Binyu Luo; Shuai Qi; Cai’e Wang; Rong Rong; Lin Ma; Jianhui Xu; Tao Zhang; Yanfu Bai; et al. (Agriculture, Ecosystems & Environment, 2027)

Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Flexural behavior and crack resistance of joints in hot-rolled section steel-UHPC composite deck under negative bending: Experiments and analysis - Wenyong Cai; Xudong Shao; Junhui Cao; Yang Wen; Rong Chen; Taowei Wang; Lin Peng; Lei Yu (Engineering Structures, 2026)

Microalgae-based bioremediation of reverse osmosis concentrate (ROC): Mechanisms, techno-economic bottlenecks, and circular bioeconomy perspectives - Na-Hui Hao; Jun Li; Ya-Rong Qi; Zhuo Chen; Yu-Ming Wang; Yu-Jia Gao; Xu-Cheng Cai; Yu Hong; Hong-Ying Hu; Yin-Hu Wu (Desalination, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Secondary forest succession shifts soil carbon priming from microbial to mineral control through dynamic microbe–mineral coupling - Panpan Wu; Jing Zhang; Xi'an Cai; Zhijian Mou; Yue Li; Wenjia Wu; Tengteng Li; Rong Mao; Zhanfeng Liu (Soil Biology and Biochemistry, 2026)

Ambient PM2.5 exposure and sleep quality: Evidence from circadian DNA methylation signatures in a population-based study - Yuting Wang; Shuzhen Liu; Jiahui Rong; Yaxin Luo; Siyuan Niu; Peifeng Guo; Xu Tang; Yujian Liang; Xiaoting Mo; Linhai Zhao; Shiwen Jiang; Tiantian Gu; et al. (Journal of Hazardous Materials, 2026)

Ni/Cu co-doped modified Bi2WO6 microsphere for enhanced photocatalytic reduction of CO2 toward CO - Xiaolong Cai; Baiquan Jing; Rong Li; Baowei Cao; Jinbo Cao; Yunhua Xu (Chemical Engineering Journal, 2026)

Geomorphic filtering of pollen signals across a reef-to-basin transect and its implications for paleoenvironmental reconstruction in the Xisha archipelago, South China Sea - Jiani Chen; Sui Wan; Wei Li; Yi Zhong; Rong Xiang; Xiang Su; Chuanxiu Luo; Dizhu Cai (CATENA, 2026)

A new benzoate derivative from Talaromyces fusiformis , an endophytic fungus cultured from Hypecoum leptocarpum Hook. f. et. Thoms - Cai-xia Li; Ting An; Hui Tan; Rong Guo; Huai-Xiu Wen (Natural Product Research, 2026)

The convergence of food-derived bioactive peptides and organoids: model construction, application, challenges and outlooks - Haowen Chen; Shuguang Wang; Jianping Wu; Jing Chen; Shulong Cai; Rong Xu; Jucai Xu; Lin Zheng; Mouming Zhao (Trends in Food Science & Technology, 2026)

Extracellular polymeric substances: overlooked contributors to soil organic carbon persistence - Yichao Wu; Yuwei Yi; Minsu Kim; Samuel Bickel; Ming Zhang; Ke Dai; Chunhui Gao; Chenchen Qu; Chuisi Kong; Mengxi Feng; Ke-Qing Xiao; Hans-Curt Flemming; et al. (Soil Biology and Biochemistry, 2026)

High-Precision baseflow separation in data-scarce regions with machine learning models - Rong Zhong; Hang Lyu; Xiaosi Su; Tingting Deng; Aimin Cai; Yanxi Wu; Jingzun Mao; Peng Zhou (Journal of Hydrology, 2026)

Metabolic rewiring of Phanerochaete chrysosporium to enhance tolerance and degradation of aged polystyrene microplastics: Pyruvate metabolism and actin polarization - Yongkang Wu; Zelin Hou; Yin Lu; Rong Cai; Jiawei Huang; Yu Mao; Ningjia Dong; Hong Liang; Dawen Gao (Journal of Hazardous Materials, 2026)

Identification of novel α-glucosidase inhibitory peptides from the serum of Xinjiang Bactrian camels - Menghui Lin; Xiaogang Guo; Rong Sun; Thanh Ninh Le; Minjie Zhao; Haiying Cai (Food Bioscience, 2026)

The synthesis of alkaline earth metal-organic framework based on asymmetric triazine hexacarboxylic acid and iodine capture performance - Shao Bin Xu; He Qun Cai; Rong Huo; Ting Zhang; Jing Jin; Yong Heng Xing; Feng Ying Bai (Environmental Research, 2026)

pH-responsive, self-lubricating hyaluronic acid-chondroitin sulfate-chitosan hydrogel for articular cartilage repair - Haofeng Qiu; Jingfang Zheng; Zheyu Yao; Ximing Cai; Gaoke Pan; Xufeng Mao; Xin Zhao; Lei Shao; Dangsheng Xiong; Rong Wang; Yi Zhang (Carbohydrate Polymers, 2026)

How does the green transition shape the structure of regional socio-ecological networks? evidence from the Yangtze river economic belt - Dongdong Gao; Xin Gao; Rong Chen; Shuangjiao Cai; Jie Tian (Environment, Development and Sustainability, 2026)

Synthesis and production of hydroxytyrosol derivatives with potent anti-inflammatory activities - Te-Sheng Chang; Wen-Yueh Ho; Jiumn-Yih Wu; Chien-Yu Wu; Pei-Rong Cai; Bo Eng Cheong; Wilson Thau Lym Yong; Peik Lin Teoh (Natural Product Research, 2026)

Strength characteristics, durability, and microstructure properties of GGBS-PG-CCS stabilized dredged marine silt - Yajun Liu; Yang Zheng; Yindong Sun; Ke Wu; Haijun Lu; Gan Cai; Rong Chen (Marine Georesources & Geotechnology, 2026)

Contamination characteristics and airflow regulated transport of microbial aerosols in a hospital respiratory ward - Lina Hu; Zhijian Liu; Guangpeng Yao; Zikai Shang; Chenxing Hu; Lianhe Lu; Rui Rong; Tong Zhou; Duo Cai (Journal of Hazardous Materials, 2026)

Changes in flavor profiles and microbial community diversity throughout rice wine fermentation with Rhizopus oryzae from different sources - Ting Tong; Jing-Rong Hu; Zhen-Jia Li; Zi-Zhen Qin; Cai-Hua Shi; Han-Cheng Wang (International Journal of Food Microbiology, 2026)

Corrigendum to “Neomycin-sensitive gut bacteria-derived brassicasterol mediates the anti-obesity effects of Cordyceps militaris polysaccharide” [Food Res. Int. 230 (2026) 118574] - Jie Cai; Aohuan Huang; Linghui You; Zelin Wang; Chaoyang Huang; Rong Huang; Ying Li; Tingting Liang; Fen Zhang; Qingping Wu; Juan Wang; Zhenjun Zhu; et al. (Food Research International, 2026)

Ion-gas synergistically reshape microenvironment for bone immune regulation and osteogenic regeneration - Kun Wang; Zhenhua Wang; Bing Xiao; Chang Cai; Jiaqiang Zhang; Yifan Zhang; Liuzhi Wu; Yelin Wu; Ke Rong; Xiaoxing Xie; Guohua Xu (Chemical Engineering Journal, 2026)

Evaluation of the aerosol transmission patterns and the airflow organization effectiveness in the respiratory outpatient clinic - Yongxin Wang; Lei Jiang; Zhijian Liu; Duo Cai; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Building and Environment, 2026)

Isolation, identification, and disease-protective potential of Pseudomonas monsensis DBFF02 against Saprolegnia infection in grass carp - Guofan Zhang; Kunyan Li; Yuyuan Peng; Simei He; Chen Li; Rong Fan; Jiajie Xie; Linger Qian; Xinran Long; Jiayi Wang; Jiatao Yang; Yanmin He; et al. (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Effects of immobilized enzymes on soil dissolved organic matter and microbial functional traits during benzo[a]pyrene bioremediation - Rong Cai; Zelin Hou; Yongkang Wu; Guanyu Chen; Tianhao Tong; Dawen Gao (Journal of Environmental Chemical Engineering, 2026)

Iron-microbe synergy in laccase deactivation and PAH bioremediation：Insights from four contrasting soils - Guanyu Chen; Zelin Hou; Rong Cai; Huayu Tao; Yongkang Wu; Hong Liang; Dawen Gao (Journal of Environmental Chemical Engineering, 2026)

Green derivative synchronous fluorescence spectroscopy approach for rapid quantification of Rhodamine B in food samples - Hong-Jun Liu; Jia-Rong He; Yi-Han Guo; Jia-Lin Li; Wei-Peng Cai; Ping-Ping Wu; Yao-Qun Li (Food Control, 2026)

Diversity and taxonomic revision of Hoya (Apocynaceae, Asclepiadoideae) in China based on morphological and molecular evidence - Yang Liu; Wang Xi; Nie-Rong Lu; Ji-Dong Ya; Jing-Feng Zhang; Lei Cai (Plant Systematics and Evolution, 2026)

Formation, Potential, and Challenges of Marine-Continental Transitional Shale Gas in China - Caineng Zou; Dazhong Dong; Qin Zhang; Weiliang Kong; Wen Liu; Zhenyu Zhao; Zhi Yang; Qun Zhao; Rong Ding; Guangyin Cai; Tianquan Qu; Wanli Gao; et al. (Journal of Earth Science, 2026)

Global meta-analysis reveals nutrient-dependent symbiosis: Perennial legumes gain microbial advantages under nitrogen/phosphorus enrichment - Hai-Xia Duan; Chong-Liang Luo; Muhammad Maqsood Ur Rehman; Sheng-Rong Chen; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2026)

Late-spring vertical profiles in atmospheric water vapor stable isotopes reveal westerlies moisture transport across the Himalaya into the Asian Water Towers - Jing Gao; Jingjing Yang; Gebanruo Chen; Yigang Liu; Xiaowei Niu; Aibin Zhao; Yilong Wang; Rong Cai; Zeqing He; Taihua Zhang; Tandong Yao (Science Bulletin, 2026)

Methionine-driven covalent chelation of Zn2+ by linusorb: a paradigm in hydrophobic cyclic peptide metal binding - Yi-kang Zhang; Du-jian Deng; Zhong-yi Luo; Wan-nan Wang; Jun-le Li; Shao-rong Zhang; Jia-li Li; Jia-zi Chen; Yong Wang; Zi-zhe Cai (Food Chemistry, 2026)

Sensitivity analysis and multi-objective particle swarm optimization (MOPSO) of a hollow fiber membrane module for the solar-based heating and humidification system - Si Zeng; Peng Peng; Nan-Feng Li; Cai-Hang Liang; Rong-Hui Qi; Yan-fang Dong; Yu-Kui Men; Jia-Hui Li; Gui-Yin Li (Energy and Buildings, 2026)

Sorption and degradation of α-terpineol in soils with distinct physicochemical properties - Huan-Feng Chen; Zi-Jun Yang; Hai-Rong Chen; Hai-Ming Zhao; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Lei Xiang (Environmental Geochemistry and Health, 2026)

Apportioning nitrate sources via dual isotope, PMF and SIAR in a complex urban river network during flood season: Implications for engineered mitigation strategies - Xin Wang; Qiaoyun Lin; Zhixiong Huang; Yihua Cai; Wenjing Wang; Nan Rong; Siye Wei; Renren Wu; Quan Zhou (Journal of Water Process Engineering, 2026)

Association between plasma trace metals and non-alcoholic fatty liver disease among rural women in Southern China - Qiumei Liu; Xiaolin Li; Yufu Lu; Kaisheng Teng; Xiaoting Mo; Linhai Zhao; Songju Wu; Jiahui Rong; Qinyi Guan; Lei Luo; Tiantian Zhang; Yujian Liang; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Neomycin-sensitive gut bacteria-derived brassicasterol mediates the anti-obesity effects of Cordyceps militaris polysaccharide - Jie Cai; Aohuan Huang; Linghui You; Zelin Wang; Chaoyang Huang; Rong Huang; Ying li; Tingting Liang; Fen Zhang; Qingping Wu; Juan Wang; Zhenjun Zhu; et al. (Food Research International, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Superenhancer-driven SMC4 promotes myeloma growth by epigenetically enhancing IFI16-dependent STING signaling - Jiayun Guan; Xuanyi Lin; Zhenfeng Dai; Jianbiao Zhou; Zhen Cai; Tze King Tan; Tae-Hoon Chung; Xiaochen Zhang; Wee-Joo Chng; Xiaoxiang Rong; Yunlu Jia (Apoptosis, 2026)

Aquaporin-1 stabilizes β-catenin to promote NLRP3 inflammasome-mediated pyroptosis in rheumatoid arthritis - Meng-yuan Zhou; Zi-yao Gao; Jing Sun; Wen-cai Long; Juan Zhou; Wen-jing Fang; Xue-chun Wang; Sheng-dong Wu; Rong Li (Apoptosis, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Short-term black carbon exposure impairs mental health and DNA methylation signatures of mitochondrial carrier genes - Shuzhen Liu; Yaxin Luo; Jiansheng Cai; Yuting Wang; Jiahui Rong; Xiaoting Mo; Yujian Liang; Zeyan Ye; Xu Tang; Siyuan Niu; Tiantian Zhang; Lei Luo; et al. (Journal of Hazardous Materials, 2026)

Phase shifts in precipitation isotope seasonality across East Asia track monsoon dynamics - Zhongyin Cai; Rong Li; Lide Tian; Chenxi Xu; Gabriel J. Bowen (Global and Planetary Change, 2026)

Tailoring a simplified and steady-state kombucha consortium for newly-formulated kiwifruit beverage production: Impacts on untargeted/targeted metabolites, antioxidant capacities and flavor profiles - Shiqi Li; Keying Chu; Rong Guo; Jiamin Wu; Xingnan Wang; Jing Guo; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Research International, 2026)

Impact of complex inhibitors in straw hydrolysates on xylose-fermenting Saccharomyces cerevisiae and inhibitor-tolerant strain construction - Xue-Xue Ji; Bo Li; Rong-Rong Chen; Zi-Yuan Xia; Cai-Yun Xie; Yue-Qin Tang (Fungal Biology, 2026)

Corrigendum to “Spectral properties and remote sensing of snow algal blooms in the Antarctic Peninsula” [Remote Sensing of Environment, volume 328 (2025), 114839]. - Barjeece Bashir; Dong Liang; Rong Cai; Faisal Mumtaz; Lingyi Kong; Yahui Zou (Remote Sensing of Environment, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

From origin tracing, processing, to quality regulation: Molecular mechanism advances in medicinal foods research by integrating multi-omics tools - Jian-Hang Cai; Guan-Dong Fang; Yan Zhang; Jie Song; Jia-Yi Weng; Xue-Mei Ge; Issoufou Amadou; Xiang-Rong Cheng (Food Bioscience, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

VSIG4 Inhibits Microglia-Mediated Neuroinflammation and Neuronal Injury by Modulating the JAK2-STAT3/NF-κB Signaling Pathway in Parkinson’s Disease - Jingcong Zhuang; Pingping Cai; Zhongjie Chen; Quanlong Hong; Rong Wang; Feng Wang; Yaxin Zhang; Danjie Wu; Fengzhu Chen (Molecular Neurobiology, 2026)

Research on decoupling and characterization methods of geological elements based on pre-stack seismic data - Cong Ren; Rong-rong Zhao; Ming-yi Li; Jing-jing Zong; Han-peng Cai; Wenhao Li (Applied Geophysics, 2025)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Can diets alleviate constipation and promote bowel movement? Exploring the underlying mechanisms of effects - Xi Gui; Lan Wu; Kaijun Huang; Rong Zeng; Xinyi Zhao; Anna Yang; Xinyi Yin; Shengbao Cai; Junjie Yi; Chuanqi Chu (Food Research International, 2025)

A peptidomics-based investigation of the synergistic effects of neutral and Alcalase proteases on release of antioxidant peptides from soybean protein isolates - Shulong Cai; Liqi Fan; Dan Liu; Changxing Wei; Na Yang; Xichao Fu; Rong Tang; Jucai Xu; Sheng Yin; Xin Chen (Food Chemistry, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Molecular modeling aided design, synthesis and biological evaluation of quinazoline derivatives for the treatment of human cancer - Cai-Shi Liu; Jin-Peng Tong; Ze-Yu Fang; Xiao-Meng Guo; Ting-Ting Shi; Shou-Rong Liu; Juan Sun (Molecular Diversity, 2025)

Silencing aquaporin 1 inhibits autophagy to exert anti-rheumatoid arthritis effects in TNF-α-induced fibroblast-like synoviocytes and adjuvant-induced arthritis rats - Man-yu Zhang; Meng-qing Wang; Yan Huang; Sheng-long Gu; Meng-yuan Zhou; Ze-shan Xu; Ling-ling Li; Min Lv; Li Cai; Rong Li (Inflammation Research, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

Fracture evolution from micropore changes to macro failure of coal samples with static-dynamic loads based on dislocation and energy theory - Yuchu Cai; Shugang Li; Xiangguo Kong; Zhihao Rong; Di He (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Atmospheric controls on precipitation isotopes in North China and their response to record-breaking torrential rainfall - Zhongyin Cai; Rong Li; Cheng Wang; Lide Tian (Journal of Hydrology, 2025)

Morphology and nutrient content of bamboo rhizomes: Responses to enclosure succession in a Phyllostachys edulis forest in Wuyi Mountains, China - Xing Cai; Rui Cheng; Zhenhua Chen; Jiannan Lin; Min Wu; Jiaying Liu; Jihong Xiao; Yuchen Lin; Lingyan Chen; Yirong Zhang; Jundong Rong; Tianyou He; et al. (Forest Ecology and Management, 2025)

Fermentation-derived dihydroferulic acid from Cordyceps militaris binds AKT1 to protect intestinal epithelial health - Rong Huang; Jixing Gao; Zelin Wang; Jie Cai; Zhenjun Zhu; Qingping Wu; Juan Wang; Fen Zhang; Yu Ding (Food Bioscience, 2025)

Spectral properties and remote sensing of snow algal blooms in the Antarctic Peninsula - Barjeece Bashir; Dong Liang; Rong Cai; Faisal Mumtaz; Lingyi Kong; Yahui Zou (Remote Sensing of Environment, 2025)

Airborne bioaerosol transmission in hospital waiting corridor: Characteristic, exposure risk and evaluation of prevention strategies - Zhijian Liu; Duo Cai; Chenxing Hu; Lei Jiang; Yongxin Wang; Lina Hu; Rui Rong; Shiyue Li; Jingwei Liu; Jiajun Feng (Journal of Hazardous Materials, 2025)

Spatial-temporal isotope patterns in European winter precipitation reflect atmospheric circulation modes over North Atlantic and Arctic Oceans - Qiyao Fan; Zhongyin Cai; Rong Li; Cheng Wang; Songlin Yu; Xinyi Yu; Lide Tian (Global and Planetary Change, 2025)

Community metagenomics, widely targeted metabolomics and volatilomics analysis reveal dynamic mechanism and correlation pattern in kombucha - Shiqi Li; Shuo Zhang; Rong Liu; Leran Wang; Xingnan Wang; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Bioscience, 2025)

Temporal-spatially metabolic reprogramming rewires the landscape of H3K27 acetylation to enable the initiation of liver regeneration - Qi Zheng; Xiaojiaoyang Li; Fanghong Li; Zhenyu Xu; Yajie Cai; Changmeng Li; Xiaoyong Xue; Shuo Li; Rong Sun; Guifang Fan; Jianzhi Wu; Jiaorong Qu; et al. (Science Bulletin, 2025)

Contrasting Pacific Decadal Oscillation influence on ice core dust deposition across the Tibetan Plateau - Cheng Wang; Lide Tian; Zhongyin Cai; Lili Shao; Ju Huang; Rong Li; Chenhao Xu; Zixiang Zhao (Quaternary Science Reviews, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Microbial electrotrophs-driven molecular transformations of dissolved organic matter in paddy soil - Rong Tang; Xiaoshan Luo; Wenjie He; Xixi Cai; Lingyan Huang; Lihua Zhou; Yong Yuan (Journal of Environmental Management, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Straw-derived bio-organic fertilizer enhanced ecosystem multifunctionality in acidic paddy by improving microbial community composition and functional diversity - Feilong Rong; Yuanshan Lin; Manyun Zhang; Zhengwu Cai; Liqun Wu; Falin Chen (Journal of Environmental Management, 2025)

Impact of cyclolinopeptide (linusorb) on oxidative stability of hot-pressed flaxseed oil and their interaction with phospholipid - Jia-hui Yu; Shao-rong Zhang; Yue Du; Du-jian Deng; Yi-kang Zhang; Jun-le Li; Li-jun Hu; Wenyi Chen; Xin Yue; Yong Wang; Jiazi Chen; Zi-zhe Cai (Food Chemistry, 2025)

Associations between plasma multi-metal exposure and mild renal impairment: Cross-sectional evidence of the potential mediating role of HDL-C in rural China - Kaisheng Teng; Qinyi Guan; Xiaoting Mo; Qiumei Liu; Lei Luo; Jiahui Rong; Tiantian Zhang; Wenjia Jin; Linhai Zhao; Songju Wu; Jiansheng Cai; Zhiyong Zhang; et al. (Toxicology and Applied Pharmacology, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Transitional chromitites within the Maqsad crust-mantle transition zone of the Semail ophiolite formed above the nascent forearc setting - Rong-Zhong Bo; Peng-Jie Cai; Dong-Yang Lian; Jing-Sui Yang; Sobhi Nasir; Hui-Chao Rui; Yu-Xiao Lu; Chu-Qi Cao; Ahmed E. Masoud (Lithos, 2025)

Association of multi-metal exposure with hyperuricemia in middle-aged and older adults: A cross-sectional study in rural Guangxi, China - Qinyi Guan; Kaisheng Teng; Qiumei Liu; Songju Wu; Lei Luo; Linhai Zhao; Jiahui Rong; Wenjia Jin; Tiantian Zhang; Mo Xiaoting; Cai Jiansheng; Zhiyong Zhang; et al. (Journal of Trace Elements in Medicine and Biology, 2025)

Microenvironment modulation of two-dimensional defective carbon nitride with extended nanoporous furnished oxygen-enriched sites for efficient recovery of rare earth elements - Hui Cai; Meng Rong; Siqi Liang; Qike Wang; Qiyu Meng; Shan Ni; Huizhou Liu; Liangrong Yang (Journal of Hazardous Materials, 2025)

QTL Mapping and Candidate Gene Analysis for Wax Trait of Stem and Leaf in Durum Wheat (Triticum turgidum L. ssp. durum (Desf.)) - Yijing Cai; Yasir Muhammad; Yujie Zhou; Yuefen Cao; Junkang Rong; Xin Hu (Plant Molecular Biology Reporter, 2025)

Combining Cirrus and Aerosol Corrections for Improved Reflectance Retrievals over Turbid Waters from Visible Infrared Imaging Radiometer Suite Data - Bo-Cai Gao; Rong-Rong Li; Marcos J. Montes; Sean C. McCarthy (Oceans, 2025)
The multi-band atmospheric correction algorithms, now referred to as remote sensing reflectance (Rrs) algorithms, have been implemented on a NASA computing facility for global remote sensing of ocean color and atmospheric aerosol parameters from data acquired with several satellite instruments, including the Visible Infrared Imaging Radiometer Suite (VIIRS) on board the Suomi spacecraft platform. These algorithms are based on the 2-band version of the SeaWiFS (Sea-Viewing Wide Field-of-View Sensor) algorithm. The bands centered near 0.75 and 0.865 μm are used for atmospheric corrections. In order to obtain high-quality Rrs values over Case 1 waters (deep clear ocean waters), strict masking criteria are implemented inside these algorithms to mask out thin clouds and very turbid water pixels. As a result, Rrs values are often not retrieved over bright Case 2 waters. Through our analysis of VIIRS data, we have found that spatial features of bright Case 2 waters are observed in VIIRS visible band images contaminated by thin cirrus clouds. In this article, we describe methods of combining cirrus and aerosol corrections to improve spatial coverage in Rrs retrievals over Case 2 waters. One method is to remove cirrus cloud effects using our previously developed operational VIIRS cirrus reflectance algorithm and then to perform atmospheric corrections with our updated version of the spectrum-matching algorithm, which uses shortwave IR (SWIR) bands above 1 μm for retrieving atmospheric aerosol parameters and extrapolates the aerosol parameters to the visible region to retrieve water-leaving reflectances of VIIRS visible bands. Another method is to remove the cirrus effect first and then make empirical atmospheric and sun glint corrections for water-leaving reflectance retrievals. The two methods produce comparable retrieved results, but the second method is about 20 times faster than the spectrum-matching method. We compare our retrieved results with those obtained from the NASA VIIRS Rrs algorithm. We will show that the assumption of zero water-leaving reflectance for the VIIRS band centered at 0.75 μm (M6) over Case 2 waters with the NASA Rrs algorithm can sometimes result in slight underestimates of water-leaving reflectances of visible bands over Case 2 waters, where the M6 band water-leaving reflectances are actually not equal to zero. We will also show conclusively that the assumption of thin cirrus clouds as ‘white’ aerosols during atmospheric correction processes results in overestimates of aerosol optical thicknesses and underestimates of aerosol Ångström coefficients.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Foliar-applied zinc promotes cadmium allocation from leaf surfaces to grains in rice - Ya-Ting Liu; Bo-Fang Yan; Xuan Cai; Hong-Xiang Zheng; Rong-Liang Qiu; Ye-Tao Tang (Journal of Environmental Sciences, 2025)

Interfacial clustering-derived fluorescent, mechanically strong and fire-safe epoxy composites - Dong-Qing Zeng; Xin-Miao Li; Feng Chen; Wei-Bin Bai; Yu-Cai Lin; Rong-Kun Jian (Chemical Engineering Journal, 2025)

Nanomedicine constructed with plant-derived aromatic aldehydes treats low back pain by reversing the progression of lumbar facet joint osteoarthritis - Ming Yang; Hui Lv; Zhenzhen Tang; Jiangling Zhou; Qiandong Yang; Juan Cai; Yingtao Gui; Bo Yu; Rong Huang; Jing Yang; Ying Bao; Dinglin Zhang; et al. (Chemical Engineering Journal, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

SIRT5: a potential target for discovering bioactive natural products - Yuwei Xie; Nali Cai; Xiaohua Liu; Liangliang He; Yiming Ma; Changyu Yan; Juan Liang; Shu-Hua Ouyang; Ao Luo; Yingzhi He; Jun Lu; Dang Ao; et al. (Journal of Natural Medicines, 2025)
Silent information regulator 5 (SIRT5) is the fifth member of the sirtuin family, which is mainly expressed in mitochondrial matrix. SIRT5 plays a key role in metabolism and antioxidant responses, and is an important regulator for maintaining intracellular homeostasis. Given its involvement in multiple cellular processes, dysregulation of SIRT5 activity is associated with a variety of diseases. This review explores the structural characteristics of SIRT5 that influence its substrate specificity, highlights recent research advances, and summarizes its four key enzymatic activities along with their corresponding substrates in disease contexts. We also discuss the natural products that modulate SIRT5 activity and identify potential targets of SIRT5 through virtual docking, which may provide new therapeutic avenues. Although the mechanism of SIRT5 in diseases needs to be further elucidated and deglutathionylation activities are still at an early stage, targeting SIRT5 and its substrates holds significant promise for the development of novel therapeutics. Graphical abstract

First report of Colletotrichum siamense causing anthracnose on Evodia rutaecarpa in Hunan, China - Mengshan Sun; Jin Xie; Liu Cai; Rong Song; Li Zhou (Journal of Plant Pathology, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Comparative analysis of three extraction methods for ginger leaf polysaccharide: Chemical composition, antioxidant activity, and hypolipidemic effects - Zhong-hao Zhang; Zhong-hua Zhao; Tian-yi Cao; Cai-rong Yang; Zi-zhong Tang; Shi-ling Feng; Shu Yuan; Sheng-lin Hu; Ming Yuan (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

A multi-perspective understanding of population change in migratory species: A case study with pied avocets (Recurvirostra avosetta) in East Asia - Yang Wu; Weipan Lei; Entao Wu; Han Pan; Yifei Jia; Cai Lu; Yongxiang Han; Junjie Wang; Rong Fan; Zhijun Ma; Zhengwang Zhang; Richard A. Fuller (Biological Conservation, 2025)

Legume intercropping improves soil organic carbon stability in drylands: A 7-year experimental validation - Wei Wang; Meng-Ying Li; Yang Wang; Jian-Ming Li; Wei Zhang; Qin-Hui Wen; Shuang-Jin Huang; Guang-Rong Chen; Shuang-Guo Zhu; Jing Wang; Fazal Ullah; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2025)

Water competition among coexisting plants in rock-dominated habitats of subtropical karst desertification - Lulu Cai; Kangning Xiong; Ziqi Liu; Yuan Li; Dayun Zhu; Yating Mu; Yi Chen; Rong Zhou; Xiaoyu Yan (Agriculture, Ecosystems & Environment, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

Voagafries A–E, undescribed indole alkaloids with anti-glioma activity from Voacanga africana - Cai-Feng Ding; Ma-Long Qin; Kun-Ying Zhao; Wen Gao; Shan-Ze Yin; Xian-Guang Hu; Gui-Guang Cheng; Rong-Ping Zhang; Wei-Yan Hu (Phytochemistry, 2025)

Phylogenomics of Paragymnopteris (Cheilanthoideae, Pteridaceae): Insights from plastome, mitochondrial, and nuclear datasets - Jing Zhao; Zhen-Long Liang; Shao-Li Fang; Rong-Juan Li; Chuan-Jie Huang; Li-Bing Zhang; Tanner Robison; Zhang-Ming Zhu; Wen-Jing Cai; Hong Yu; Zhao-Rong He; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2025)

A shear-responsive and lubricating hyaluronic acid-chondroitin sulfate-decellularized matrix hydrogel for articular cartilage regeneration - Haofeng Qiu; Gaoke Pan; Xufeng Mao; Ximing Cai; Lei Song; Lei Shao; Haijiao Mao; Rong Wang; Dangsheng Xiong (Carbohydrate Polymers, 2025)

Leukemia inhibitory factor promotes growth and maintains stemness in giant panda MSCs - Feiping Li; Yuliang Liu; Mengshi Zhang; Shenfei Wang; Xianbiao Hu; Xiangyu Liu; Rong Hou; Kailai Cai (In Vitro Cellular & Developmental Biology - Animal, 2025)

Drug–drug interaction of phenytoin sodium and methylprednisolone on voriconazole: a population pharmacokinetic model in children with thalassemia undergoing allogeneic hematopoietic stem cell transplantation - Yun Wu; Lu-lu Niu; Ya-yun Ling; Si-ru Zhou; Tian-min Huang; Jian-ying Qi; Dong-ni Wu; Rong-da Cai; Ting-qing Wu; Yang Xiao; Taotao Liu (European Journal of Clinical Pharmacology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A NIR fluorescent probe based on carbamoyl oxime with high specificity for detecting ferrous ions in food and in vivo - Caiyun Liu; Tingyi Yan; Tingting Fu; Kun Wang; Xiaodi Rong; Xueting Liu; Yao Wang; Xinyu Cai; Wenlong Sheng; Baocun Zhu (Food Research International, 2025)

Nonconventional phosphorus-based tertiary amine curing agent enabling the high fire safety, outstanding tensile strength and high glass transition temperature of epoxy resin - Xue-Qi Chen; Yu-Cai Lin; Wei-Bin Bai; Yuan-Wei Yan; Rong-Kun Jian (Chemical Engineering Journal, 2025)

Remote sensing monitoring for impact of island on chlorophyll a in the water near the Diaoyu Island (Diaoyu Dao) and its affiliated islands, China - Lina Cai; Ruohao Xin; Xiaomin Ye; Rong Tang; Jie Yin; Leichao Cheng (Acta Oceanologica Sinica, 2025)

Aphid-resistant alfalfa cultivar minimizes the survival of spotted alfalfa aphid through upregulating plant defense compounds - Kaihui Zhu; Neng Zhang; Daogang Zhang; Cai Ni; Rong Liu; Wunan Che; Ullah Hidayat; Xiongbing Tu (Crop Protection, 2025)

Structurally diversified sesquiterpenoids from Chloranthus henryi and their neuroprotective activities on H2O2 damaged PC12 cells - Meng-Li He; Lian-Lian Xu; Yang Liu; Yan-Ping Gao; Yong-Ming Luo; Rong-Cai Yue; Fang-You Chen (Phytochemistry, 2025)

The mango bacterial black spot altered the endophyte community structure and diversity - Meng-Jiao Li; Ji-Han Li; Wen-Lin Li; Yuan He; Yu-Bo Ma; Xin-Yu Li; Yan Wang; Cai-Xia Li; Xin-Rong Ma (International Journal of Food Microbiology, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Prevalence and genetic characterization of linezolid resistance gene reservoirs in hospital sewage from Zhejiang Province, China - Weiyi Shen; Yanyan Hu; Dejun Liu; Yang Wang; Stefan Schwarz; Rong Zhang; Jiachang Cai (Science of The Total Environment, 2024)

Responses of various organic carbon pools to elevated temperatures in soils - Yafeng Han; Chenchen Qu; Xiping Hu; Pan Sun; Jie Kang; Peng Cai; Xingmin Rong; Wenli Chen; Qiaoyun Huang (Science of The Total Environment, 2024)

Long-term cereal-legume intercropping accelerates soil organic carbon loss in subsoil of dryland - Wei Wang; Guang-Rong Chen; Meng-Ying Li; Yinglong Chen; Yang Wang; Hong-Yan Tao; Hui-Zhi Hou; Muhammad Maqsood Ur Rehman; Muhammad Ashraf; Yajie Song; Levis Kavagi; Bao-Zhong Wang; et al. (Resources, Conservation and Recycling, 2024)

Epidemiological and genomic analysis revealed the significant role of flies in dissemination of carbapenem-resistant Enterobacteriaceae (CRE) in China - Hongwei Zhou; Hanyu Wang; Kaichao Chen; Miaomiao Xie; Zelin Yan; Yanyan Zhang; Yuchen Wu; Dejun Liu; Juan Wang; Ning Dong; Chang Cai; Yongning Wu; et al. (Journal of Hazardous Materials, 2024)

A single-atom nanozyme-enabled strategy for rapid, visual, and real-time detection of polystyrene nanoplastics in water - Fuqiang Hu; Taimei Cai; Rong Wang; Jianwen Tian; Hailong Peng (Journal of Environmental Chemical Engineering, 2024)

Exploring the dynamic characteristic of typical kombucha induced by symbiotic microbiota succession from four Chinese regions: A comprehensive analytical framework - Shiqi Li; Ruinan Wang; Rong Liu; Leran Wang; Xingnan Wang; Jianping Wei; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Research International, 2024)

Volatile organic compounds in typical coal chemical industrial park in China and their environmental and health impacts - Jieting Zhou; Min Gao; Hongmei Xu; Ruiqing Cai; Rong Feng; Kun He; Jian Sun; Steven Sai Hang Ho; Zhenxing Shen (Atmospheric Environment, 2024)

Evolution of phosphate metabolism in Tibetan wild barley to adapt to aluminum stress - Shengguan Cai; Yuqing Huang; Yang Liu; Liyuan Wu; Dezhi Wu; Rong Liu; Peter R. Ryan; Meixue Zhou; Guoping Zhang; Zhong-Hua Chen (Plant and Soil, 2024)

The change of environmental factors in the water near the Yangtze Estuary may induce the change of large yellow croaker fishery location there - Lina Cai; Jiahua Li; Xiaojun Yan; Rong Tang; Xinkai Zhang (Frontiers in Marine Science, 2024)
The large yellow croaker, an endemic migratory species in China’s coastal waters, holds considerable economic importance. It is very necessary and significant to study the spatio-temporal evolution of large yellow croaker fishery based on environmental factors. In this paper, the HY-1C/D Coastal Zone Imager was applied to reveal distributional details of suspended sediment concentration and chlorophyll-a concentration in large yellow croaker fishery. Furthermore, combined with multi-source data, the characteristics of other environmental parameters such as temperature, salinity, current, wind and fronts were analyzed to reveal the changing of large yellow croaker fishery location. The results show that: (1) The environmental factors of large yellow croaker fishery exhibit pronounced spatial and temporal characteristics. Generally, the temperature (9-28°C), salinity (20-34 ‰) and other water environmental factors of the fishing ground are conducive to the survival and growth of large yellow croaker. The formation and change of fishery are closely related to environmental factors in the water. (2) The change of environmental factors in the water may induce the change of large yellow croaker fishery location. Winter sea surface temperature has significantly risen over the past two decades (2004-2023). With the sea surface temperature rising by approximately 2°C west of 125°E, the overwintering ground has expanded westward, increasing by nearly 29%. In addition, the scale and number of offshore windmills increased by 836% and 456% respectively over the decade (2013-2023). In 2023, offshore wind farms cover an area of 145.47 km 2 and have 200 windmills. Wind turbine piles resembling artificial reefs. It can not only promote the waters vertical exchange to enhance the nutrients in upper waters but also provide a protective base for fish spawning. Thus, effectively attracting fish species. The construction of offshore wind farms has extended spawning ground north-westward to the mouth of the Yangtze River Estuary, expanding by nearly 21%. This study improved the cognition level of resources, habitat environment and change trend of large yellow croaker. It also provided technical support for the construction and protection of the large yellow croaker fishery.

White matter lesions contribute to motor and non-motor disorders in Parkinson’s disease: a critical review - Yue-Qi Jiang; Qiu-Zhu Chen; Yang Yang; Cai-Xia Zang; Jing-Wei Ma; Jin-Rong Wang; Yi-Rong Dong; Ning Zhou; Xing Yang; Fang-Fang Li; Xiu-Qi Bao; Dan Zhang (GeroScience, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

Study on the Rules of Ground Settlement and Pipeline Deformation Considering the Combined Effects of Pipeline Damage Leakage and Shield Tunneling Construction - Xin Shi; Liang Zheng; Chuanxin Rong; Hua Cheng; Haibing Cai; Taihong Li (Transportation Geotechnics, 2024)

Study on Translational toxicology of Senna obtusifolia aqueous extract - Xin Guo; Liping Gong; Chong Guo; Taotao Cai; Nana Huang; Xianhui Shen; Lisong Sheng; Rongrong Li; Yanqing Wang; Xinmei Zhao; Wenhe Guo; Rong Sun (Toxicon, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Preparation of super toughened flame-retardant polylactic acid with an in situ hyperbranched structure by reactive blending with a phosphorus-containing copolyester and hexamethylene glycidyl cyclotriphosphazene - Guozhang Gu; Huaiyang Cai; Yutao Wang; Chen Tang; Guoxiang Zou; Jinchun Li; Rong Yang (Chemical Engineering Journal, 2024)

Scalable and facile fabrication of sulfonic-acid-functionalized porous hypercrosslinked polymers for efficient recovery of rare earth elements from tailing wastewater - Siqi Liang; Qiyu Meng; Zhiqian Liu; Hui Cai; Huizhou Liu; Meng Rong; Liangrong Yang (Chemical Engineering Journal, 2024)

Quantifying the biodiversity and ecosystem service outcomes of karst ecological restoration: A meta-analysis of South China Karst - Yue Chen; Cai Cheng; Kangning Xiong; Li Rong; Shihao Zhang (CATENA, 2024)

Ferroptosis and Pyroptosis in Epilepsy - Fan Feng; Rong Luo; Dezhi Mu; Qianyun Cai (Molecular Neurobiology, 2024)

Numerical study on thermal–hydraulic behaviors of a natural circulation system with petal-shaped fuel rod bundle - Jian-Chuang Sun; Rong-Jiang Zhou; Xiang-Fei Meng; Jin-Yi Cao; Wen-Chao Zhang; Jin-Cheng Wang; Wei-Hua Cai (Annals of Nuclear Energy, 2024)

Glutamine deprivation in glioblastoma stem cells triggers autophagic SIRT3 degradation to epigenetically restrict CD133 expression and stemness - Zhengcao Xing; Xianguo Jiang; Yalan Chen; Tiange Wang; Xiaohe Li; Xiangyun Wei; Qiuju Fan; Jie Yang; Hongmei Wu; Jinke Cheng; Rong Cai (Apoptosis, 2024)

Numerical Analysis of Leading-Edge Roughness Effects on the Aerodynamic Performance of a Thick Wind Turbine Airfoil - Wei Zhang; Kuichao Ma; Chang Cai; Xiangyu Sun; Jun Zhang; Xiaohui Zhong; Xiaomin Rong; Qing’an Li (Journal of Marine Science and Engineering, 2024)
The aerodynamic performance of wind turbine airfoils is crucial for the efficiency and reliability of wind energy systems, with leading-edge roughness significantly impacting blade performance. This study conducts numerical simulations on the DU 00-W-401 airfoil to investigate the effects of leading-edge roughness. Results reveal that the rough airfoil exhibits a distinctive “N”-shaped lift coefficient curve. The formation mechanism of this nonlinear lift curve is primarily attributed to the development of the trailing-edge separation vortex and variations in the adverse pressure gradient from the maximum thickness position to the trailing-edge confluence. The impact of different roughness heights is further investigated. It is discovered that when the roughness height is higher than 0.3 mm, the boundary layer can be considered fully turbulent, and the lift curve shows the “N” shape stably. When the roughness height is between 0.07 mm and 0.1 mm, a transitional state can be observed, with several saltation points in the lift curve. The main characteristics of different flow regimes based on different lift curve segments are summarized. This research enhances the understanding of the effects of leading-edge roughness on the aerodynamic performance of a thick wind turbine airfoil, and the simulation method for considering the effect of leading-edge roughness is practical to be applied on large-scale wind turbine blade to estimate the aerodynamic performance under rough leading-edge conditions, thereby supporting advancements in wind turbine technology and promoting the broader adoption of renewable energy.

Preliminary analysis of the indicators and accumulation models of gas hydrates in the central Zhongjiannan Basin, western South China sea - Zhou-rong Cai; Xin Sui; Yong-jian Yao; Zheng-xin Yin; Xiao-dong Yang; Dong Ju; Rong-wei Zhu; Xiao-xiang Wang; Huo-dai Zhang (Marine and Petroleum Geology, 2024)

Enzymatically green-produced bacterial cellulose nanoparticle-stabilized Pickering emulsion for enhancing anthocyanin colorimetric performance of versatile films - Shiqi Li; Rong Liu; Jiale Zhao; Shuo Zhang; Xuerong Hu; Xingnan Wang; Zhenpeng Gao; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Chemistry, 2024)

Enhancing vitamin D3 bioaccessibility: Unveiling hydrophobic interactions in soybean protein isolate and vitamin D3 binding via an infant in vitro digestion model - Jia-Rong Huang; Jing-Ru Song; Wan-Shuang Cai; Zhen-Wen Shao; Da-Yong Zhou; Liang Song (Food Chemistry, 2024)

Interface Modulation of 2D Superlattice Heterostructures with Oxygen-enriched Sites and Dissolution Restraint for Effective Rare-earth Elements Extraction - Hui Cai; Meng Rong; Qiyu Meng; Zhiqian Liu; Siqi Liang; Shan Ni; Liangrong Yang (Chemical Engineering Journal, 2024)

Nitrogen removal performance and mechanism in constructed wetlands under saline conditions: Role of Canna indica inoculated with Piriformospora indica - Naxin Cui; Min Cai; Xu Zhang; Rong Zeng; Li Zhou; Guifa Chen; Guoyan Zou (Bioresource Technology, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Microbial etch: A novel construction method of functionalized biochar for enhanced uranium extraction in radioactive wastewater - Yazhou Wang; Xudong Wu; Xiyang Liu; Chengkun Cai; Chenghu Liang; Lichun Dai; Xinsheng He; Rong He; Huanhuan Liu; Wenkun Zhu (Chemosphere, 2024)

Evolution and disappearance of the paleo-West Pacific Anomaly: Implications to the future of South Atlantic Anomaly - Yaochen Yue; Jiawei Gao; Fei He; Yong Wei; Shuhui Cai; Huapei Wang; Yuqi Wang; Zhaojin Rong; Zhonghua Yao; Wei Lin; Yongxin Pan (Physics of the Earth and Planetary Interiors, 2024)

Evolution and deposition patterns of turbidity currents under complex vegetation canopies - Jiayi Li; Yantun Song; Chongfa Cai; Liwen Qiu; Rong Hao; Changhua Zhan; Qiong Yang (Journal of Hydrology, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

Polydatin: a potential NAFLD therapeutic drug that regulates mitochondrial autophagy through SIRT3-FOXO3-BNIP3 and PINK1-PRKN mechanisms - a network pharmacology and experimental investigation - Jing He; Yi-cai Qian; Ying-chuan Yin; Jing-rui Kang; Tian-rong Pan (Chemico-Biological Interactions, 2024)

Toxic nonpreferred species accelerate the natural restoration of plant productivity and diversity in degraded grasslands - Xiaona Zheng; Chen Chen; Xin Dai; Le Lang; Xing Li; Jigui Chen; Rong Wang; Wenhui Cai; Ying Gao (Science of The Total Environment, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

A deep learning network for improving predictions of maximum and minimum temperatures over complex terrain - Lin Xu; Li Zhou; He Chen; Rong-Hui Cai; Yue Zhou (Theoretical and Applied Climatology, 2024)

Pleurotus eryngii root waste and soybean meal co-fermented protein improved the growth, immunity, liver and intestinal health of largemouth bass (Micropterus salmoides) - Jian-Ming Xu; Wen-Rong Gao; Ping Liang; Guo-He Cai; Hong-Ling Yang; Jian-Bin Lin; Yun-Zhang Sun (Fish & Shellfish Immunology, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Study on spray characteristics of micro-nano bubble premixed fuel - Rong Xuan; Liang Guo; Ningning Cai; Wanchen Sun; Yuying Yan; Hao Zhang; Yanling Chen; Han Wang; Junfeng Zhang; Youxin Ge (Fuel, 2024)

Ultrafine Ru clusters with GOx enable glucose-activated cascaded reaction for bacterial-infected diabetic wound healing - Lu Zhang; Shuangqi Cai; Yujie Zhai; Rong Huang; Shenglin Pei; Fei Lin; Weiqing Zhang (Chemical Engineering Journal, 2024)

Differential surface modification mechanism of chalcopyrite and pyrite by Thiobacillus ferrooxidans and its response to bioflotation - Chao Su; Jinpeng Cai; Qifang Zheng; Rong Peng; Xingcai Yu; Peilun Shen; Dianwen Liu (Bioresource Technology, 2024)

Ultrafine FeCuAgCeGd–based high–entropy nanozyme: Preparation, catalytic mechanism, and point–of–care detection of dopamine in human serum - Rui Sheng; Yue Liu; Taimei Cai; Rong Wang; Gan Yang; Tao Wen; Fangjian Ning; Hailong Peng (Chemical Engineering Journal, 2024)

27-Hydroxycholesterol inhibits trophoblast fusion during placenta development by activating PI3K/AKT/mTOR signaling pathway - Xiaoyan Zhao; Xiaxia Cai; Haiyan Zhu; Qinyu Dang; Qian Yang; Yandi Zhu; Yadi Zhang; Mengling Zhang; Xinyin Jiang; Zhuo Hu; Yuchen Wei; Rong Xiao; et al. (Archives of Toxicology, 2024)

The environmental analysis and site selection of mussel and large yellow croaker aquaculture areas based on high resolution remote sensing - Lina Cai; Jie Yin; Xiaojun Yan; Yongdong Zhou; Rong Tang; Menghan Yu (Acta Oceanologica Sinica, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Iridoids and other constituents from the leaves and stems of Valeriana officinalis var. latifolia - Jia-Jin Liu; Jun-Jie Hao; Min Tan; Cai-Cen Liao; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2024)

Functionalized hydrogen-bonded organic superstructures via molecular self-assembly for enhanced uranium extraction - Yafeng Liu; Shan Ni; Wenjie Wang; Meng Rong; Hui Cai; Huifang Xing; Liangrong Yang (Journal of Hazardous Materials, 2024)

Bi-directional prediction of hydrothermal carbonization characteristics of agroforestry and livestock wastes with variable components: Graph learning model-aided waste recycle - Zi-Kai Lin; Chao-Sheng Li; Rong-Rong Cai; Yan-Qiu Long (Journal of Cleaner Production, 2024)

Determination of tetrodotoxin in bivalve mollusks by hydrophilic interaction liquid chromatography-triple quadrupole mass spectrometry with internal standard calibration and its contamination in Zhejiang province, China - Ming-rong Qian; Hui-zhen Wu; Zeng-xuan Cai; Mei-jia Xu; Jian-long Han; Xiao-min Xu (Food Chemistry, 2024)

Ferroptosis: underlying mechanisms and involvement in neurodegenerative diseases - Yi Wang; HongJing Li; QianXiong He; Rong Zou; JinRui Cai; Lin Zhang (Apoptosis, 2024)

Early Jurassic Gypsum within Eastern African Continental Marginal Basins and Its Significance for Gas Play - Jun Cai; Rong Guo (Journal of Marine Science and Engineering, 2024)
Although the eastern African continental marginal basins have discovered giant gas fields, it is not clear whether the Early Jurassic gypsum associated with the main source rocks controls the gas play. In this paper, we use well logging, seismic reflection, and organic geochemistry data to synthesize the distribution and origin of the gypsum deposits and their control over the gas play. The results show that from 201 Ma to 183 Ma, a thick suite of mudstone with thin-layered gypsum began to form in the southern gulf-like sea due to water stratification. With the sea level falling since 183 Ma, a thick suite of gypsum was deposited in some grabens, where the sedimentary environment changed to lagoons. The gypsum increases the maturity threshold depth of Lower Jurassic source rocks and delays the peak time of gas generation, resulting in the ongoing filling of East African natural gas reservoirs and the formation of giant reserves. In addition, the gypsum not only controls the distribution of conventional gas but also makes the Lower Jurassic shale, where the faults are not developed, an important place for shale gas exploration in the future due to the good sealing properties of the gypsum.

NixSy/NF composites assembled by sulfidation of nickel foam (NF) for highly effective capture of iodine - Bo Qiao; Haiqing Yan; Chaonan Wang; Huiqin Yao; Zidan Cai; Keren Shi; Rong Liu; Shulan Ma (Chemical Engineering Journal, 2024)

Interfacial coordination-assisted construction of mechanically robust, fluorescent and intumescent flame retardant epoxy resins - Xin-Miao Li; Wei-Bin Bai; Yu-Cai Lin; Fu-Chuan Ding; Rong-Kun Jian (Chemical Engineering Journal, 2024)

Recognizing topological attributes and spatiotemporal patterns in spotted seals (Phoca largha) trophic networks based on eDNA metabarcoding - Yan Xu; Fei Huang; Mingliang Zhou; Rui Gu; Jie Zhu; Qiangqiang Rong; Yanpeng Cai (Frontiers in Marine Science, 2023)
Spotted seals, a protected species, face multifaceted threats to their habitat, which in turn impact the closely associated trophic networks. These threats will lead to irreversible structural variations within the ecosystem. Therefore, investigating the topological variability of trophic networks in spotted seals is important. Applying environmental DNA methods, field sample collection was conducted in 2021 during both the sea fishing moratorium period and the fishing period to decode fish diversity. Assessing the current status of fish resources by using the multivariate statistics approach. Applying dietary information establishes the spotted seals’ trophic network. Selecting 12 network indexes to analyze the spatiotemporal patterns of network topological attributes. As a result, about 51 families, and 76 genera species were identified. During the sea fishing moratorium and the fishing period, there are 12 and 18 different food resources available for spotted seals, respectively. The diversity index revealed that the FP had greater species richness and diversity than the SP. Comparatively, the Fishing period exhibited higher species richness and biodiversity, likely influenced by habitat heterogeneity and anthropogenic activities. Additionally, the topological features of networks reflected the high clustering coefficients (CC=0.35) and the proportion of omnivorous species (O≈60%), indicating that the network structure in this region tends to form higher trophic-level clustering patterns, which facilitate the formation of weaker interactions between clusters, enhancing the robustness of the network. The higher connectivity complexity index during the fishing period (SC=12.3) supported that the spotted seal’s trophic network was relatively more stable in this period. Thus, during the fishing period, it is crucial to pay more attention to the intensity of human fishing on mid-to-high trophic-level omnivorous fish resources to ensure the sustainability of these potential food resources for spotted seals. This comprehensive study achieved three key objectives: (a) utilizing eDNA to characterize fish diversity during distinct periods, (b) establishing trophic networks of spotted seals, and (c) discerning topological attributes and spatiotemporal patterns within the ecological network. Overall, this study can provide technical and data support for integrated ecological network management and propose suggestions for protecting and recovering spotted seals.

Responses of antibiotic resistance genes in the enhanced biological phosphorus removal system under various antibiotics: Mechanisms and implications - Ligui Wu; Qiaofeng Wu; Jingcheng Xu; Lingling Rong; Xiaoli Yu; Chen Cai; Xiangfeng Huang; Xiaoming Zou (Science of The Total Environment, 2023)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Research progress of main synthetic catalysts used in biomass pyrolysis - Hongwei Rong; Penghong He; Yuxin Luo; Haizhen Cai; Mahmood Laghari; Dabin Guo; Yan Ren; Baihui Cui (Process Safety and Environmental Protection, 2023)

Injectable, tough and adhesive zwitterionic hydrogels for 3D-printed wearable strain sensors - Jiating Liu; Yueyun Zhou; Jiawei Lu; Rong Cai; Tian Zhao; Ying Chen; Mengxue Zhang; Xiang Lu; Yi Chen (Chemical Engineering Journal, 2023)

High phytoplankton diversity in eutrophic states impedes lake recovery - Rong Wang; C. Patrick Doncaster; Wenxiu Zheng; Min Xu; Hui Yang; Yun Li; Yongjiu Cai; Yanjie Zhao; Enlou Zhang; Xiangdong Yang; Boqiang Qin (Journal of Biogeography, 2023)
Aim The widely observed positive response of productivity to biodiversity, known as the biodiversity‐productivity relationship (BPR), underpins nature‐based solutions for mitigating and adapting to global changes. Little is known of the role of such emergent processes in the restoration of damaged ecosystems. Here, we test for evidence of a BPR in degraded freshwater lakes, and its role in underpinning or undermining lake recovery from eutrophic states. Location Lower Yangtze and Huaihe river basins, China, East Asia. Taxa Freshwater phytoplankton; also macrophytes, fish, zooplankton and zoobenthos. Methods A systematic review of biodiversity studies was conducted to enumerate freshwater biodiversity change during eutrophication, encompassing 572 samples from 155 lakes in East China. Empirical samples were then taken of 93 phytoplankton communities from 38 lakes in ecologically degraded states of eutrophication. Samples were analysed for niche overlap in relation to biodiversity and productivity, and metrics of network structure indicative of community stability. Results Reviewed publications on eutrophication in East China lakes revealed losses in biodiversity of macrophytes, fishes, zooplankton and zoobenthos but not phytoplankton. Empirically sampled eutrophic lakes maintained high phytoplankton biodiversity through niche differentiation, and phytoplankton biodiversity correlated positively with biomass, in line with the expectations of BPR. Conclusions The positive effect of biodiversity on phytoplankton productivity in eutrophic lakes acts in opposition to the negative impacts on productivity induced by eutrophication‐management strategies of nutrient suppression. In degraded systems, the BPR contributes to sustaining productivity of lake phytoplankton communities, impeding recovery from a eutrophic state. This is a case of the BPR playing an undesirable role at the ecosystem level. Lake recovery programmes need to anticipate that the control of phytoplankton biomass will depend on reducing nutrients to a level sufficient to degrade the internal structure of the phytoplankton community.

Prostate Cancer, Oxidative Stress, and Antioxidant Phytochemicals: A Brief Review - Shanyi Li; Tong Cai; Shichen Cui; Fangmin Liu; Rong Hu; Wenji Li (Current Pharmacology Reports, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Pogocablenes A-O, fifteen undescribed sesquiterpenoids with structural diversity from Pogostemon cablin - Shu-Yi Li; Yu-Mei Feng; Yan Zhou; Cai-Cen Liao; Lu Su; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2023)

Structure-diversified terpenoids from Salvia prattii and their protective activity against alcoholic liver diseases - Xiu-wen Yin; Xiang-xiang Bian; Yan-fang Chen; Ming Zhang; Lan Wu; Fu-cai Ren; Fu-rong Yang; Xiang-dong Pu; Bing-yuan Yang; Chuan-pu Shen (Phytochemistry, 2023)

A spheropolyhedral-based discrete element lattice Boltzmann method for simulation of non-spherical adhesive particulate flow - Ye-Cheng Qian; Rong-Rong Cai; Li-Zhi Zhang (Computer Physics Communications, 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

Genetic parameter estimates for estrus duration and urinary hormone levels in captive female giant pandas - He Huang; Shiyi Chen; Yongyou Feng; Zongjin Ye; Rong Hou; Yuliang Liu; Li Luo; Xiangming Huang; Kongju Wu; James Ayala; Kailai Cai; Jingchao Lan (Mammalian Biology, 2023)

Bacillus amyloliquefaciens Induces Resistance in Tobacco Against Powdery Mildew Pathogen Erysiphe cichoracearum - Rong Jiao; Ayesha Ahmed; Pengfei He; Shahzad Munir; Yixin Wu; Junwei Wang; Pengbo He; Ge Wang; Huanwen Yang; Jing Zhao; Canhua Lu; Yongzhan Cai; et al. (Journal of Plant Growth Regulation, 2023)

Contrasting effects of rice husk and its biochar on N2O emissions and nitrogen leaching from Lei bamboo soils under subtropical conditions - Rong Zhou; Zhe Chen; Ali EI-Naggar; Linlin Tian; Chengpeng Huang; Zhen Zhang; Kumuduni Niroshika Palansooriya; Yongfu Li; Bing Yu; Scott X. Chang; Yanjiang Cai (Biology and Fertility of Soils, 2023)

Hypervirulent Klebsiella pneumoniae detection methods: a minireview - Qi-bin Zhang; Peng Zhu; Shun Zhang; Yan-jing Rong; Zuo-an Huang; Li-wan Sun; Ting Cai (Archives of Microbiology, 2023)

Bacterial community diversity and underlying assembly patterns along vertical soil profiles in wetland and meadow habitats on the Zoige Plateau, China - Hao-Cai Wang; Jin-Feng Qi; De-Rong Xiao; Yi Wang; Wei-Yu Shi; Hang Wang (Soil Biology and Biochemistry, 2023)

Emergence of the clinical rdar morphotype carbapenem-resistant and hypervirulent Klebsiella pneumoniae with enhanced adaption to hospital environment - Congcong Liu; Ning Dong; Xueting Huang; Zixian Huang; Chang Cai; Jiayue Lu; Hongwei Zhou; Jingren Zhang; Yu Zeng; Fan Yang; Gongxiang Chen; Zhangqi Shen; et al. (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The early Late Triassic Yumen mafic rocks in the eastern Tethyan Himalaya: A record of the progressive opening of the Yarlung Zangbo Neo-Tethyan Ocean - Wei-Liang Liu; Zhong-Xi Xia; Yun Zhong; Chris Yakymchuk; Zhou-Rong Cai; He Xiao; Xing Liao; Chi Yan; Ru-Xin Ding; Jin-Nan Liu (Lithos, 2023)

The acceleration on decolorization of azo dyes by magnetic lignin-based materials via enhancing the extracellular electron transfer - Rong-ping Chen; Xin-yuan Wei; Cheng-hao Gan; Bing-cai Cai; Wen-jie Xu; Shareen Niyazi; Quan Wang; Lei Yu; Hui-hua Min; Qiang Yong (Journal of Environmental Management, 2023)

Activation of Pgk1 Results in Reduced Protein Aggregation in Diverse Neurodegenerative Conditions - Hao Chen; Yajie Li; Jingwen Gao; Qi Cheng; Lei Liu; Rong Cai (Molecular Neurobiology, 2023)

Synergistic degradation of tetracycline from Mo2C/MoOx films mediated peroxymonosulfate activation and visible-light triggered photocatalysis - Zheng Lian; Ting Wu; Xining Zhang; Shuangfei Cai; Youlin Xiong; Rong Yang (Chemical Engineering Journal, 2023)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Bang-Yin Tan; Cai-Feng Ding; Rui-Rong Guo; Jing-Zhi Zhao; Di-Wei Ma; Kun Fan; Lan-Chun Zhang; Rong-Ping Zhang; Wei-Yan Hu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Natural polymer Nicandra physaloides (L.) Gaertn seed gum mediated assembly of hydroxyapatite assembly as versatile sponge for water pollution control - Xudong Wu; Yazhou Wang; Li Zhou; Chengkun Cai; Mingfang Hu; Xiaofang Yu; Rong He; Wenkun Zhu (Journal of Cleaner Production, 2023)

Association of climatic variables with risk of transmission of influenza in Guangzhou, China, 2005–2021 - Rong Zhang; Ka Yan Lai; Wenhui Liu; Yanhui Liu; Wenfeng Cai; Chris Webster; Lei Luo; Chinmoy Sarkar (International Journal of Hygiene and Environmental Health, 2023)

Characterizations of food-derived ellagic acid-Undaria pinnatifida polysaccharides solid dispersion and its benefits on solubility, dispersity and biotransformation of ellagic acid - Zhao-Rong Li; Rui-Bo Jia; Xueyuan Cai; Donghui Luo; Chong Chen; Mouming Zhao (Food Chemistry, 2023)

Corrigendum to “Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels” [Food Hydrocolloids 139 (2023) 108527] - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Inconsistent mercury records from terrestrial upland to coastal lowland across the Permian-Triassic transition - Jianbo Chen; Guangyi Sun; Binjian Lu; Rong-yao Ma; Zhuang Xiao; Yao-feng Cai; Hua Zhang; Shu-zhong Shen; Feifei Zhang; Zhuo Feng (Earth and Planetary Science Letters, 2023)

HSPA12A was identified as a key driver in colorectal cancer GWAS loci 10q26.12 and modulated by an enhancer–promoter interaction - Zequn Lu; Linyun Fan; Fuwei Zhang; Chaoqun Huang; Yimin Cai; Can Chen; Gaoyuan Li; Ming Zhang; Jinyu Huang; Caibo Ning; Yanmin Li; Wenzhuo Wang; et al. (Archives of Toxicology, 2023)

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Controllable Pd@Cu2O Schottky junction interface with improved anti-poisoning effect for efficiently electroreduction of CO2 into syngas - Rong Cai; Xin Du; Guorui Liu; Xiuli Wang; Qiang Tang; Xinpin Pan; Feng Li; Jing Li (Fuel, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Study of coexisting upstream solitary wave packet and downstream wakes induced by Diaoyu Dao and its affiliated islands detected by satellite sun glitter - Lina Cai; Xiaoqi Jiang; Xiaojun Yan; Yan Bai; Jianqiang Liu; Menghan Yu; Rong Tang; Jingjing Jiang (Acta Oceanologica Sinica, 2023)

Astaxanthin, bile acid and chlorogenic acid attenuated the negative effects of high-fat diet on the growth, lipid deposition, and liver health of Oncorhynchus mykiss - Wei Zhao; Rong Yao; Han-Lin Wei; Yu-Cai Guo; An-Qi Chen; Bao-Yang Chen; Jin-Niu (Aquaculture, 2023)

A resident subsea docking system with a real-time communication buoy moored by an electro-optical-mechanical cable - Chengye Cai; Zhenwei Rong; Zheng Chen; Bo Xu; Zhanglin Wang; Sijie Hu; Yingqiang Wang; Mingru Dong; Xiangqian Quan; Yulin Si; Ying Chen; Haocai Huang (Ocean Engineering, 2023)

Microbiota-mediated reactivation of triclosan oxidative metabolites in colon tissues - Hongna Zhang; Katherine Z. Sanidad; Jianan Zhang; Guangqiang Wang; Rong Zhang; Chengchen Hu; Yongfeng Lin; Thomas D. Haggerty; Julie Parsonnet; Yuxin Zheng; Guodong Zhang; Zongwei Cai (Journal of Hazardous Materials, 2023)

Flexible three-dimensional covalent organic frameworks for ultra-fast and selective extraction of uranium via hydrophilic engineering - Xiao-Juan Chen; Cheng-Rong Zhang; Xin Liu; Jia-Xin Qi; Wei Jiang; Shun-Mo Yi; Cheng-Peng Niu; Yuan-Jun Cai; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Carbon dots as light-responsive oxidase-like nanozyme for colorimetric detection of total antioxidant capacity in fruits - Jinquan Li; Yun Zhou; Yue Xiao; Shuo Cai; Changsheng Huang; Shuo Guo; Yuanqiang Sun; Rong-Bin Song; Zhaohui Li (Food Chemistry, 2023)

Fertility assessment and nutrient conversion of hydrochars derived from co-hydrothermal carbonization between livestock manure and corn cob - Chao-sheng Li; Rong-rong Cai; Abdulla Hasan; Xiao-luan Lu; Xiao-xiao Yang; Yan-guo Zhang (Journal of Environmental Chemical Engineering, 2023)

DNA Methylation Alterations and Their Association with High Temperature Tolerance in Rice Anthesis - Bo Li; Haiya Cai; Ke Liu; Bingzhuang An; Rong Wang; Fang Yang; Changli Zeng; Chunhai Jiao; Yanhao Xu (Journal of Plant Growth Regulation, 2023)
DNA methylation is an important epigenetic mechanism involved in gene regulation under environmental stresses in plants. However, little information is available regarding its responses to high temperature (HT) and association with HT tolerance in rice. In this study, fourteen rice genotypes were classified into the susceptible, moderate, and tolerant groups by the high temperature susceptibility index (HTSI) after HT treatment. The changes of DNA methylation in rice anthesis under normal and HT30 conditions were investigated using methylation-sensitive amplified polymorphism31 (MSAP). The MSAP results showed that the DNA methylation level significantly increased in the susceptible rice group and decreased in the tolerant rice group under HT treatment, while no significant difference was observed in the moderate rice group. More hypomethylation events were detected in the tolerant rice group, while more hypermethylation was detected in the susceptible rice group. Forty-four differentially methylated epiloci (DME) were generated under both control and HT conditions, which can clearly distinguish the susceptible, moderate, and tolerant genotypes via PCoA analysis. Approximately 43.18% of DMEs were determined to be tolerance-associated epiloci (TAEs). 63.15% TAEs were sequenced and annotated into 12 genes. Quantitative RT-PCR analysis showed that 12 TAE genes were mainly upregulated in 14 rice genotypes, and their expression levels were related to the HT tolerance of rice. Here, DEGs, generated from a number of genotypes, indicate higher probabilities for association with stress tolerance. Overall, these results suggest that DNA methylation regulation might play a key role in adaptation to HT stress in rice.

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Iridoids and sesquiterpenoids from Valeriana officinalis and their bioactivities - Dao-Qun Shi; Jia-Jin Liu; Yu-Mei Feng; Yan Zhou; Cai-Cen Liao; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2023)

Effects of different pretreatment methods on drying kinetics, three-dimensional deformation, quality characteristics and microstructure of dried apple slices - Jun-Wen Bai; Lu Zhang; Joshua H. Aheto; Jian-Rong Cai; Yu-Chi Wang; Li Sun; Xiao-Yu Tian (Innovative Food Science & Emerging Technologies, 2023)

A self-supported sodium alginate composite hydrogel membrane and its performance in filtering heavy metal ions - Rong Cai; Ying Chen; Jiawei Hu; Jinli Xiong; Jiawei Lu; Jiating Liu; Xiaobo Tan; Wenyong Liu; Yueyun Zhou; Yi Chen (Carbohydrate Polymers, 2023)

Radiomics based on readout-segmented echo-planar imaging (RS-EPI) diffusion-weighted imaging (DWI) for prognostic risk stratification of patients with rectal cancer: a two-centre, machine learning study using the framework of predictive, preventive, and personalized medicine - Zonglin Liu; Yueming Wang; Fu Shen; Zhiyuan Zhang; Jing Gong; Caixia Fu; Changqing Shen; Rong Li; Guodong Jing; Sanjun Cai; Zhen Zhang; Yiqun Sun; et al. (EPMA Journal, 2022)
Background Currently, the rate of recurrence or metastasis (ROM) remains high in rectal cancer (RC) patients treated with the standard regimen. The potential of diffusion-weighted imaging (DWI) in predicting ROM risk has been reported, but the efficacy is insufficient. Aims This study investigated the potential of a new sequence called readout-segmented echo-planar imaging (RS-EPI) DWI in predicting the ROM risk of patients with RC using machine learning methods to achieve the principle of predictive, preventive, and personalized medicine (PPPM) application in RC treatment. Methods A total of 195 RC patients from two centres who directly received total mesorectal excision were retrospectively enrolled in our study. Machine learning methods, including recursive feature elimination (RFE), the synthetic minority oversampling technique (SMOTE), and the support vector machine (SVM) classifier, were used to construct models based on clinical-pathological factors (clinical model), radiomic features from RS-EPI DWI (radiomics model), and their combination (merged model). The Harrell concordance index (C-index) and the area under the time-dependent receiver operating characteristic curve (AUC) were calculated to evaluate the predictive performance at 1 year, 3 years, and 5 years. Kaplan‒Meier analysis was performed to evaluate the ability to stratify patients according to the risk of ROM. Findings The merged model performed well in predicting tumour ROM in patients with RC at 1 year, 3 years, and 5 years in both cohorts (AUC = 0.887/0.813/0.794; 0.819/0.795/0.783) and was significantly superior to the clinical model (AUC = 0.87 [95% CI: 0.80–0.93] vs. 0.71 [95% CI: 0.59–0.81], p = 0.009; C-index = 0.83 [95% CI: 0.76–0.90] vs. 0.68 [95% CI: 0.56–0.79], p = 0.002). It also had a significant ability to differentiate patients with a high and low risk of ROM (HR = 12.189 [95% CI: 4.976–29.853], p < 0.001; HR = 6.427 [95% CI: 2.265–13.036], p = 0.002). Conclusion Our developed merged model based on RS-EPI DWI accurately predicted and effectively stratified patients with RC according to the ROM risk at an early stage with an individualized profile, which may be able to assist physicians in individualizing the treatment protocols and promote a meaningful paradigm shift in RC treatment from traditional reactive medicine to PPPM.

Adsorption properties and mechanism of ginkgo biloba leaf-based materials for Cd (II) in aqueous solution - Yan-rong Cai; Yang Song; Chun Chang (Environmental Science and Pollution Research, 2022)

The spatial-temporal consistency of chlorophyll-a and fishery resources in the water of the Zhoushan archipelago revealed by high resolution remote sensing - Lina Cai; Rong Tang; Xiaojun Yan; Yongdong Zhou; Jingjing Jiang; Menghan Yu (Frontiers in Marine Science, 2022)
Details of the chlorophyll- a (Chl- a ) distribution in the water of the Zhoushan archipelago were analyzed based on data from the panchromatic multispectral sensor (PMS) of the GaoFen-6 (GF-6). A new Chl- a inversion model was built using in-situ Chl- a and the green-red bands of the 2 m spatial resolution GF-6/PMS image. Combined with fishery data, the relationship between Chl- a concentration and fish resources were revealed. The results show that: (1) High Chl- a concentration area was mainly concentrated in the nearshore intensive islands waters, and Chl- a concentration changes obviously with the change of tidal currents. Chl- a concentration around islands increases, especially downstream of islands. Seasonally, Chl- a concentration is higher in spring and summer, lower in autumn, and lowest in winter. (2) The change of fish eggs and larvae in the water of the Zhoushan archipelago shows consistency with the spatial distribution and seasonal variation of Chl- a . (3) The interaction between tidal currents and islands results in the diverse currents (upstream upwelling and downstream vortex currents) around the islands, promoting vertical water exchange and the uplifting of nutrients, resulting in a high overall Chl- a concentration in the waters around the islands. The diverse flow conditions, the ideal nutrient-rich environment, and the abundant phytoplankton attract a large number of fish to gather and breed in the waters around the islands. (4) Chl- a of intensive island waters is an essential indicator for fish spawning grounds.

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Sugar Product Diversification and Its Opportunities in China - Qi Wang; Cai-Feng Xie; Chang-Rong Shi; Yuan Li; Yu-Hao Shang; Chu-Xuan Hou; Fang-Xue Hang; Jian-Bin Li; Kai Li (Sugar Tech, 2022)

Runoff projections of the Qinling Mountains and their impact on water demand of Guanzhong region in Northwest China - Zhao-peng Zhang; Ke-qin Duan; Huan-cai Liu; Ya-li Meng; Rong Chen; Da-wei Li; Shuang-shuang Li (Journal of Mountain Science, 2022)

Identifying Supercooled Liquid Water in Cloud Based on Airborne Observations: Correlation of Cloud Particle Number Concentration with Icing Probability and Proportion of Spherical Particles - Yuquan Zhou; Can Song; Miao Cai; Siyao Liu; Yang Gao; Rong Zhang (Journal of Meteorological Research, 2022)

Somatic embryogenesis in Rosa chinensis cv. ‘Old Blush’ - Yanfang Cai; Lintao Tang; Haixia Chen; Yufan Li; Rong Liu; Jiren Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Analysis of Grain Yield Formation Components of Extra Heavy-Panicle-Type Mid-Season Indica Hybrid Rice - Xiaolong Zhong; Hafiz Athar Hussain; Bingbing Zhao; Manyu Huang; Saddam Hussain; Rong Xie; Linjun Cai; Han Yun; Guanghua He; Changwei Zhang (Journal of Plant Growth Regulation, 2022)

Sodium tanshinone IIA sulfonate improves cognitive impairment via regulating Aβ transportation in AD transgenic mouse model - Hui-Han Ma; Can Wan; Lu-Di Zhang; Rong-Rong Zhang; Dong Peng; Li-Jun Qiao; Shi-Jie Zhang; Ye-Feng Cai; Hong-Qiang Huang (Metabolic Brain Disease, 2022)

Effect of biochar on transformation of dissolved organic matter and DTPA-extractable Cu and Cd during sediment composting - Meihua Zhao; Caiyuan Cai; Zhen Yu; Hongwei Rong; Chaosheng Zhang; Shungui Zhou (Environmental Science and Pollution Research, 2022)

Bioactive isocoumarins isolated from a mangrove-derived fungus Penicillium sp. MGP11 - Rong-Qing Mei; Bin Wang; Wei-Nv Zeng; Guo-Lei Huang; Guang-Ying Chen; Cai-Juan Zheng (Natural Product Research, 2022)

The establishment of giant panda (Ailuropoda melanoleuca) fibroblast cell line - Yuliang Liu; Jiasong Chen; Tongying Feng; Rong Hou; Zhigang Cai; Donghui Wang; Mingyue Zhang; Yuan Li; Yijiao Chen; Junhui An (In Vitro Cellular & Developmental Biology - Animal, 2022)

Control of chronic obstructive pulmonary disease in urban populations: findings from a cross-sectional prevalence survey in Shenzhen, China - Le-Cai Ji; Jin-Feng Yin; Chun-Rong Lu; Hong-Yun Guan; Wei-Guo Tan; Ling-Wei Wang; Qi Jiang (Environmental Science and Pollution Research, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Inclusion of Ecological Water Requirements in Optimization of Water Resource Allocation Under Changing Climatic Conditions - Wencong Yue; Zhongqi Liu; Meirong Su; Meng Xu; Qiangqiang Rong; Chao Xu; Zhenkun Tan; Xuming Jiang; Zhixin Su; Yanpeng Cai (Water Resources Management, 2022)

The combined toxicity and mechanism of multi-walled carbon nanotubes and nano zinc oxide toward the cabbage - Mo Hong; Ji-Lai Gong; Wei-Cheng Cao; Rong Fang; Zhe Cai; Jun Ye; Zeng-Ping Chen; Wang-Wang Tang (Environmental Science and Pollution Research, 2022)

Dietary pectin caused great changes in bile acid profiles of Pelteobagrus fulvidraco - Xiamin Cao; Shengjie Ren; Chunfang Cai; Qin Ni; Xinyue Li; Yunhe Meng; Zijing Meng; Ye Shi; Huangen Chen; Rong Jiang; Ping Wu; Yuantu Ye (Fish Physiology and Biochemistry, 2021)

Circulating microRNA-30a-5p, microRNA-101-3p, microRNA-140-3p and microRNA-141-3p as potential biomarkers for dexmedetomidine response in pediatric patients - Xinmei Cai; Bilian Li; Wei Wei; Yanping Guan; Xue Bai; Min Huang; Yaying Huang; Lili Rong; Xingrong Song; Guoping Zhong (European Journal of Clinical Pharmacology, 2021)

One new α , β -unsaturated 7-ketone sterol from the mangrove-derived fungus Phomopsis sp.MGF222 - Xiao-Chen Zhu; Guo-Lei Huang; Rong-Qing Mei; Bin Wang; Xue-Ping Sun; You-Ping Luo; Jing Xu; Cai-Juan Zheng (Natural Product Research, 2021)

A new phenol derivative isolated from mangrove-derived fungus Eupenicillium sp. HJ002 - Rong-Qing Mei; Xu-Hua Nong; Bin Wang; Xue-Ping Sun; Guo-Lei Huang; You-Ping Luo; Cai-Juan Zheng; Guang-Ying Chen (Natural Product Research, 2021)

Influencing factors and physiochemical changes of embryogenesis through in vitro isolated microspore culture in Brassica species - Yan-Qi Dong; Yu-Hong Gao; Te Zhao; Guang-Qian Ren; Yan-Li Liu; Bin Guan; Rong-Xian Jin; Fei Gao; Yan-Li Zhang; Xiu-Fang Tan; Hong-Cai Zhu; Yu-Hong Zhang; et al. (Biologia, 2021)

A temperature-induced chitosanase bacterial cell-surface display system for the efficient production of chitooligosaccharides - Qianqian Li; Tuantuan Wang; Yangzhi Ye; Shimin Guan; Baoguo Cai; Shuo Zhang; Shaofeng Rong (Biotechnology Letters, 2021)

Converting rice husk to biochar reduces bamboo soil N2O emissions under different forms and rates of nitrogen additions - Rong Zhou; Ali El-Naggar; Yongfu Li; Yanjiang Cai; Scott X. Chang (Environmental Science and Pollution Research, 2021)

Mucor rongii sp. nov., a New Cold-Tolerant Species from China - Feirong Bai; Su Yao; Chengshan Cai; Tianci Zhang; Yu Wang; Wei Liu; Baowen Ma; Changyuan Rong; Chi Cheng (Current Microbiology, 2021)

Isolation, culture, and characterization of cells derived from giant panda (Ailuropoda melanoleuca) semen - Yuliang Liu; Yuan Li; Rong Hou; Zhigang Cai; Donghui Wang; Jiasong Chen; Feiping Li; Yijiao Chen; Junhui An (In Vitro Cellular & Developmental Biology - Animal, 2021)

A stochastic epidemic model coupled with seasonal air pollution: analysis and data fitting - Sha He; Sanyi Tang; Yongli Cai; Weiming Wang; Libin Rong (Stochastic Environmental Research and Risk Assessment, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Important Factors Influencing the Implementation of Independent Port State Control Regimes - Chien-Chung Yuan; Rong-Her Chiu; Cunqiang Cai (Journal of Marine Science and Engineering, 2020)
This study investigated the factors influencing the implementation of a port state control (PSC) system. The analytical hierarchy process (AHP) was employed to develop a framework including 4 dimensions and 14 factors for assessing the priority of the major factors and subfactors. An expert questionnaire was conducted in Taiwan. The priority levels of the factors in influencing PSC operation are presented herein. In addition, conclusions were derived from an empirical case study of Taiwan. Some challenges are also discussed to reveal the common problems and special difficulties faced by independent PSC regimes that remain excluded from regional memoranda of understanding.

The isolation and culture of giant panda (Ailuropoda melanoleuca) breast milk cells - Chen Yijiao; Wang Donghui; Liu Yuliang; Li Feiping; He Ping; Cai Zhigang; Zhang Hao; Chen Min; Hou Rong; An Junhui (In Vitro Cellular & Developmental Biology - Animal, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Estradiol regulates the expression of CD45 splicing isoforms in lymphocytes - Tianwei Zhang; Zhaoxia Dong; Haitao Cai; Ju Rong; Zhongjing Su (Molecular Biology Reports, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Three functional variants were identified to affect RPS24 expression and significantly associated with risk of colorectal cancer - Danyi Zou; Hongli Zhang; Juntao Ke; Jiaoyuan Li; Ying Zhu; Yajie Gong; Yang Yang; Jianbo Tian; Yi Zhang; Xiating Peng; Kailin Cai; Rong Zhong; et al. (Archives of Toxicology, 2020)

Fluorescence “Off-On” Probe for L-Cysteine Detection Based on Nitrogen Doped Carbon Dots - Yin-long Xu; Rong-biao Bai; Cai-yu Qi; Zeng Ren; Xiu-zhi Jia; Zi-gui Kan; Cao-long Li; Fei Wang (Journal of Fluorescence, 2019)

New pyrazinoquinazoline alkaloids Isolated from a culture of Stenotrophomonas maltophilia QB-77 - Sheng-Yan Qian; Cai-Ling Yang; Afsar Khan; Rong-Xiang Chen; Ming-Song Wu; Li Tuo; Qian Wang; Jian-Guo Liu; Gui-Guang Cheng (Natural Product Research, 2019)

Two new benzophenones and one new natural amide alkaloid isolated from a mangrove-derived Fungus Penicillium citrinum - Cai-Juan Zheng; Hai-Xia Liao; Rong-Qing Mei; Guo-Lei Huang; Lu-Jia Yang; Xue-Ming Zhou; Tai-Ming Shao; Guang-Ying Chen; Chang-Yun Wang (Natural Product Research, 2019)

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

Study on the grossular rabbit with high hardness excavated from Yin Ruins, Anyang, China - Rong Wang; Lu Cai; Tian-tian Bao; Ji-gen Tang; Chang-sui Wang (Archaeological and Anthropological Sciences, 2019)

Correction to: Complete chloroplast genome of Firmiana major (Malvaceae), a critically endangered species endemic to southwest China - Ji‑Dong Ya; Zhi‑Xiang Yu; Yong-Qiong Yang; Shu‑Dong Zhang; Zhi‑Rong Zhang; Jie Cai; Jun‑Bo Yang; Wen‑Bin Yu (Conservation Genetics Resources, 2018)

Complete chloroplast genome of Firmiana major (Malvaceae), a critically endangered species endemic to southwest China - Ji-Dong Ya; Zhi-Xiang Yu; Yan-Qiong Yang; Shu-Dong Zhang; Zhi-Rong Zhang; Jie Cai; Jun-Bo Yang; Wen-Bin Yu (Conservation Genetics Resources, 2018)

Origin and genetic family of Huhehu oil in the Hailar Basin, northeast China - Yao-Ping Wang; Fan Zhang; Yan-Rong Zou; Zhao-Wen Zhan; Yulan Cai (Acta Geochimica, 2018)

A simulation–optimization modeling approach for watershed-scale agricultural N2O emission mitigation under multi-level uncertainties - Ronghua Xu; Yanpeng Cai; Zhifeng Yang; Qian Tan; Wen Xu; Qiangqiang Rong (Stochastic Environmental Research and Risk Assessment, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Transcriptome analysis of differentially expressed genes in rabbits’ ovaries by digital gene-expression profiling - Tao Huang; Ya-dong Wang; Ming-ming Xue; Xue Feng; Cai-Xia Sun; An-si Wang; Shu-yu Xie; Meng Zhang; Gui-Rong Sun; Ming Li (Genes & Genomics, 2018)

Correction to: Risk exposure assessment of per- and polyfluoroalkyl substances (PFASs) in drinking water and atmosphere in central eastern China - Zhibo Lu; Rong Lu; Hongyuan Zheng; Jing Yan; Luning Song; Juan Wang; Haizhen Yang; Minghong Cai (Environmental Science and Pollution Research, 2018)

Risk exposure assessment of per- and polyfluoroalkyl substances (PFASs) in drinking water and atmosphere in central eastern China - Zhibo Lu; Rong Lu; Hongyuan Zheng; Jing Yan; Luning Song; Juan Wang; Haizhen Yang; Minghong Cai (Environmental Science and Pollution Research, 2018)

Agricultural non-point source pollution management in a reservoir watershed based on ecological network analysis of soil nitrogen cycling - Wen Xu; Yanpeng Cai; Qiangqiang Rong; Zhifeng Yang; Chunhui Li; Xuan Wang (Environmental Science and Pollution Research, 2018)

Productive functional evolution of rural settlements: analysis of livelihood strategy and land use transition in eastern China - Bai-lin Zhang; Guang-hui Jiang; Wei-min Cai; Pi-ling Sun; Feng-rong Zhang (Journal of Mountain Science, 2017)

Bioorganic fertilizer maintains a more stable soil microbiome than chemical fertilizer for monocropping - Feng Cai; Guan Pang; Rui-Xia Li; Rong Li; Xiao-Long Gu; Qi-Rong Shen; Wei Chen (Biology and Fertility of Soils, 2017)

A new flavonoid from Sophora flavescens Ait. - Rong Huang; Yi Liu; Lin-Lin Zhao; Xi-xin Chen; Feng Wang; Wei Cai; Lei Chen (Natural Product Research, 2017)

Remediation mechanisms of mercapto-grafted palygorskite for cadmium pollutant in paddy soil - Xuefeng Liang; Xu Qin; Qingqing Huang; Rong Huang; Xiuling Yin; Yanming Cai; Lin Wang; Yuebing Sun; Yingming Xu (Environmental Science and Pollution Research, 2017)

Trichoderma-enriched organic fertilizer can mitigate microbiome degeneration of monocropped soil to maintain better plant growth - Guan Pang; Feng Cai; Ruixia Li; Zheng Zhao; Rong Li; Xiaolong Gu; Qirong Shen; Wei Chen (Plant and Soil, 2017)

Temperature‐mediated local adaptation alters the symbiotic function in arbuscular mycorrhiza - Rong Yang; Xiaobu Cai; Xiaolin Li; Peter Christie; Junling Zhang; Jingping Gai (Environmental Microbiology, 2017)
Summary Variation in the symbiotic function of arbuscular mycorrhizal fungi (AM fungi) has been demonstrated among distinct biotic and abiotic interactions. However, there is little knowledge on how local temperature conditions influence the functional divergence of AM symbionts in alpine ecosystems. Here, we conduct a reciprocal inoculation experiment to explore the three‐way interactions among plants, AM fungal inoculum and temperature at sites of contrasting elevation. Evidence of local adaptation of plant growth was found only under low temperature conditions, with no consistent local versus foreign effect found in AM fungal performance. The origin of either the plant or the inoculum relative to the temperature was important in explaining symbiotic function. Specifically, when inoculum and temperature were sympatric but allopatric to the plant, poor adaptation by the plant to the novel environment was clearly found under both temperature conditions. Further analysis found that the symbiotic function was inversely related to fungal diversity under high temperature conditions. These results suggest that local adaptation represents a powerful factor in the establishment of novel combinations of plant, inoculum and temperature, and confirms the importance of taking into account both biotic and abiotic interactions in the prediction of the response of symbionts to global environmental change.

Green Synthesis of Sucrose Laurate Under Different Ultrasonic Frequencies - Fang-xue Hang; Chang-rong Shi; Yong-shi Xu; Hai-qin Lu; Cai-feng Xie; Kai Li (Sugar Tech, 2017)

A novel non-ATP competitive FGFR1 inhibitor with therapeutic potential on gastric cancer through inhibition of cell proliferation, survival and migration - Jianzhang Wu; Xiaojing Du; Wulan Li; Yangyang Zhou; Encheng Bai; Yanting Kang; Qiuxiang Chen; Weitao Fu; Di Yun; Qing Xu; Peihong Qiu; Rong Jin; et al. (Apoptosis, 2017)

Fruit and vegetable consumption and risk of cardiovascular disease: A meta-analysis of prospective cohort studies - Jian Zhan; Yu-Jian Liu; Long-Biao Cai; Fang-Rong Xu; Tao Xie; Qi-Qiang He (Critical Reviews in Food Science and Nutrition, 2017)

Cloning and expression analysis of zygote arrest 1 (Zar1) in New Zealand white rabbits - DAN WANG; SHU-YU XIE; WEI ZHANG; CAI-XIA SUN; TAO HUANG; AN-SI WANG; XUE-LEI HAN; GUI-RONG SUN; MING LI (Journal of Genetics, 2017)

Pilot Demonstration of Ceramic Membrane Ultrafiltration of Sugarcane Juice for Raw Sugar Production - Wen Li; Guo-Qing Ling; Chang-Rong Shi; Kai Li; Hai-Qin Lu; Fang-Xue Hang; Yu Zhang; Cai-Feng Xie; Deng-Jun Lu; Hong Li (Sugar Tech, 2017)

Performance improvement of raw water pretreatment process with pre-inoculation biofilm: feasibility and limiting factors - Guang-feng Yang; Li-juan Feng; Cai-rong Guo; Tian Xia; Xiang-yang Xu; Liang Zhu (Biodegradation, 2017)

U–Pb dating of zircon and cassiterite from the Early Cretaceous Jiaojiguan iron-tin polymetallic deposit, implications for magmatism and metallogeny of the Tengchong area, western Yunnan, China - Hua-Wen Cao; Yun-Hui Zhang; Qiu-Ming Pei; Rong-Qing Zhang; Li Tang; Bin Lin; Guo-Jun Cai (International Geology Review, 2017)

Dual-Labeled Time-Resolved Immunofluorometric Assay for the Simultaneous Quantitative Detection of Hepatitis B Virus Antigens in Human Serum - Rong-Liang Liang; Yun-Sen Yang; Jian-Wei Zhou; Tian-Cai Liu; Xu-Ping Xu; Qian-Ni Liang; Zhen-Hua Chen; Zhi-Ning Dong; Ying-Song Wu (Journal of Fluorescence, 2017)

Trichoderma harzianum-induced resistance against Fusarium oxysporum involves regulation of nuclear DNA content, cell viability and cell cycle-related genes expression in cucumber roots - Shuang-Chen Chen; Hong-Jiao Zhao; Zhong-Hong Wang; Cai-Xia Zheng; Pu-Yan Zhao; Zhi-Hua Guan; Hai-Yang Qin; Ai-Rong Liu; Xiao-Min Lin; Golam-Jalal Ahammed (European Journal of Plant Pathology, 2017)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Effects of β-glucan on ROS production and energy metabolism in yellow croaker (Pseudosciaena crocea) under acute hypoxic stress - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Jia-Lang Zheng; Chang-Wen Wu; Rong Cai (Fish Physiology and Biochemistry, 2016)

Responses of arbuscular mycorrhizal symbionts to contrasting environments: field evidence along a Tibetan elevation gradient - Rong Yang; Shuming Li; Xiaobu Cai; Xiaolin Li; Peter Christie; Junling Zhang; Jingping Gai (Mycorrhiza, 2016)

Lack of association between rs10491334 in the CAMK4 gene and longevity in a Chinese population - RONG LIN; YUNXIA ZHANG; DONGJING YAN; XIAOPING LIAO; YUNXIN FU; WANGWEI CAI (Journal of Genetics, 2016)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Botanical Drug Puerarin Attenuates 6-Hydroxydopamine (6-OHDA)-Induced Neurotoxicity via Upregulating Mitochondrial Enzyme Arginase-2 - Jia Zhao; Yuanyuan Cheng; Chuanbin Yang; Sam Lau; Lixing Lao; Bo Shuai; Jing Cai; Jianhui Rong (Molecular Neurobiology, 2016)

Improving the antioxidant activity and enriching salvianolic acids by the fermentation of Salvia miltiorrhizae with Geomyces luteus - Yun Xing; Le Cai; Tian-peng Yin; Yang Chen; Jing Yu; Ya-rong Wang; Zhong-tao Ding (Journal of Zhejiang University-SCIENCE B, 2016)

A Fluorescence Immunochromatographic Assay Using Europium (III) Chelate Microparticles for Rapid, Quantitative and Sensitive Detection of Creatine Kinase MB - Xiao-Hong Lai; Rong-Liang Liang; Tian-Cai Liu; Zhi-Ning Dong; Ying-Song Wu; Lin-Hai Li (Journal of Fluorescence, 2016)

One-step reverse transcription loop-mediated isothermal amplification assay for rapid detection of melon yellow spot virus - Rong Zeng; Li-hui Xu; Shi-gang Gao; Xiu-hong Ni; Chun-lei Chen; Jian-cai Chen; Fu-ming Dai (European Journal of Plant Pathology, 2016)

Effects of the novel cis-nitromethylene neonicotinoid insecticide Paichongding on enzyme activities and microorganisms in yellow loam and Huangshi soils - Zhiqiang Cai; Yan Rong; Jie Chen; Jing Wang; Jiangtao Ma; Wenjie Zhang; Xiyue Zhao (Environmental Science and Pollution Research, 2016)

Textural and map contrasts of the subduction-collision boundary between the Philippine Arc and the Sunda margin - Zhou-rong Cai; Jun-yang Xiang; Qiang-tai Huang; Zheng-xin Yin; Yong-jian Yao; Hai-ling Liu; Bin Xia (Arabian Journal of Geosciences, 2016)

“Fertile island” effects of Tamarix chinensis Lour. on soil N and P stoichiometry in the coastal wetland of Laizhou Bay, China - Qiangqiang Rong; Jingtao Liu; Yanpeng Cai; Zhaohua Lu; Zhenzhen Zhao; Wencong Yue; Jiangbao Xia (Journal of Soils and Sediments, 2016)

Large-scale comparative phosphoprotein analysis of maize seedling leaves during greening - De-Li Ning; Ke-Hui Liu; Chang-Cai Liu; Jin-Wen Liu; Chun-Rong Qian; Yang Yu; Yue-Feng Wang; Ying-Chun Wang; Bai-Chen Wang (Planta, 2016)

Downregulation of ubiquitin-specific protease 14 (USP14) inhibits breast cancer cell proliferation and metastasis, but promotes apoptosis - Lianxin Zhu; Shuyun Yang; Song He; Fulin Qiang; Jing Cai; Rong Liu; Changjiang Gu; Zengya Guo; Chen Wang; Wei Zhang; Chunhui Zhang; Yingying Wang (Journal of Molecular Histology, 2016)

Geochronology, geochemistry, and Sr–Nd–Pb isotopes of Cretaceous granitoids from western Tibet: petrogenesis and tectonic implications for the evolution of the Bangong Meso-Tethys - Qiang-Tai Huang; Zhou-Rong Cai; Bin Xia; Jian-Feng Li; Lian-Ze Xia; Hui-Chuan Liu (International Geology Review, 2016)

CDK14 Contributes to Reactive Gliosis via Interaction with Cyclin Y in Rat Model of Spinal Cord Injury - Chengwei Duan; Yonghua Liu; Lu Lu; Rixin Cai; Huaqing Xue; Xingxing Mao; Chen Chen; Rong Qian; Dongmei Zhang; Aiguo Shen (Journal of Molecular Neuroscience, 2015)

Valuation of Pharmaceutical Patents: A Comprehensive Analytical Framework Based on Technological, Commercial, and Legal Factors - Jingyun Ni; Rong Shao; Carolina Oi Lam Ung; Yitao Wang; Yuanjia Hu; Yong Cai (Journal of Pharmaceutical Innovation, 2015)

Isolation and characterisation of Bacillus spp. antagonistic to Vibrio parahaemolyticus for use as probiotics in aquaculture - Xue-Fei Liu; Ya Li; Jian-Rong Li; Lu-Yun Cai; Xiu-Xia Li; Jin-Ru Chen; Shu-Xia Lyu (World Journal of Microbiology and Biotechnology, 2015)

Predicting hybrid fertility from maker-based genetic divergence index of parental varieties: implications for utilizing inter-subspecies heterosis in hybrid rice breeding - Ping Liu; Zhiwu Dan; Zhe Wang; Shaoqing Li; Nengwu Li; Huanxin Yan; Xingxing Cai; Bao-Rong Lu (Euphytica, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

The mechanism of UVB irradiation induced-apoptosis in cataract - Yinghong Ji; Lei Cai; Tianyu Zheng; Hongfei Ye; Xianfang Rong; Jun Rao; Yi Lu (Molecular and Cellular Biochemistry, 2015)

Determination of selected pharmaceuticals in tap water and drinking water treatment plant by high-performance liquid chromatography-triple quadrupole mass spectrometer in Beijing, China - Mei-Quan Cai; Rong Wang; Li Feng; Li-Qiu Zhang (Environmental Science and Pollution Research, 2015)

The rescuable function and mechanism of resveratrol on As2O3-induced hERG K+ channel deficiency - Xin Zhao; Kai-ping Zhang; Ting Huang; Cai-Chuan Yan; Li-Rong Liu; Qi-Lei Zhu; Feng-Feng Guo; Chen Liu; Bao-Xin Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Two new bicyclic sesquiterpenes from the stems of Kadsura heteroclita - Wei Su; Jian-Ping Zhao; Jian Hu; Min Yang; Melissa Jacob; Xiong Cai; Rong Zeng; Sheng-Huang Chen; Hui-Yong Huang; Ikhlas Khan; De-An Guo; Wei Wang (Natural Product Research, 2014)

Analysis of aroma-active compounds in three sweet osmanthus (Osmanthus fragrans) cultivars by GC-olfactometry and GC-MS - Xuan Cai; Rong-zhang Mai; Jing-jing Zou; Hong-yan Zhang; Xiang-ling Zeng; Ri-ru Zheng; Cai-yun Wang (Journal of Zhejiang University-SCIENCE B, 2014)

A three‐component signalling system fine‐tunes expression kinetics of HPPK responsible for folate synthesis by positive feedback loop during stress response of X anthomonas campestris - Fang‐Fang Wang; Chao‐Ying Deng; Zhen Cai; Ting Wang; Li Wang; Xiao‐Zheng Wang; Xiao‐Ying Chen; Rong‐Xiang Fang; Wei Qian (Environmental Microbiology, 2014)
Summary During adaptation to environments, bacteria employ two‐component signal transduction systems, which contain histidine kinases and response regulators, to sense and respond to exogenous and cellular stimuli in an accurate spatio‐temporal manner. Although the protein phosphorylation process between histidine kinase and response regulator has been well documented, the molecular mechanism fine‐tuning phosphorylation levels of response regulators is comparatively less studied. Here we combined genetic and biochemical approaches to reveal that a hybrid histidine kinase, SreS , is involved in the SreK ‐ SreR phosphotransfer process to control salt stress response in the bacterium X anthomonas campestris . The N ‐terminal receiver domain of SreS acts as a phosphate sink by competing with the response regulator SreR to accept the phosphoryl group from the latter's cognate histidine kinase SreK . This regulatory process is critical for bacterial survival because the dephosphorylated SreR protein participates in activating one of the tandem promoters ( P 2) at the 5′ end of the sreK ‐ sreR ‐ sreS ‐ hppK operon, and then modulates a transcriptional surge of the stress‐responsive gene hppK , which is required for folic acid synthesis. Therefore, our study dissects the biochemical process of a positive feedback loop in which a ‘three‐component’ signalling system fine‐tunes expression kinetics of downstream genes.

Age and composition of the Rebang Co and Julu ophiolites, central Tibet: implications for the evolution of the Bangong Meso-Tethys - Wei-Liang Liu; Bin Xia; Yun Zhong; Jian-Xin Cai; Jian-Feng Li; Hong-Fei Liu; Zhou-Rong Cai; Zhi-Lei Sun (International Geology Review, 2014)

Author’s Reply to Discussion of the Paper “An Empirical Failure Criterion for Intact Rocks” by Peng et al. (2013) - Jun Peng; Ming Cai; Guan Rong; Chuangbing Zhou; Xiaojiang Wang (Rock Mechanics and Rock Engineering, 2014)

An Empirical Failure Criterion for Intact Rocks - Jun Peng; Guan Rong; Ming Cai; Xiaojiang Wang; Chuangbing Zhou (Rock Mechanics and Rock Engineering, 2014)

In situ ATR-FTIR study on the adhesion of Pseudomonas putida to Red soil colloids - Huayong Wu; Wenli Chen; Xingmin Rong; Peng Cai; Ke Dai; Qiaoyun Huang (Journal of Soils and Sediments, 2014)

Relative performance of Canadian spring wheat cultivars under organic and conventional field conditions - Atif Kamran; Hiroshi Kubota; Rong-Cai Yang; Harpinder S. Randhawa; Dean Spaner (Euphytica, 2014)

Interfacial interaction between methyl parathion-degrading bacteria and minerals is important in biodegradation - Gang Zhao; Qiaoyun Huang; Xingmin Rong; Peng Cai; Wei Liang; Ke Dai (Biodegradation, 2014)

Application of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration in the Management of Mediastinal and Hilar Lymphadenopathy Without Intrapulmonary Mass: Experience from the Largest Cancer Center of Southern China - Guang-yu Luo; Pei-qiang Cai; Jie-hua He; Jian-jun Li; Yin Li; Hong-bo Shan; Rong Zhang; Xiao-yan Gao; Xiang-ming Lao; Guo-liang Xu (Cell Biochemistry and Biophysics, 2013)

Neuroprotective effects of flavonoids extracted from licorice on kainate-induced seizure in mice through their antioxidant properties - Ling-hui Zeng; Hua-dan Zhang; Cai-ju Xu; Yu-jia Bian; Xue-jiao Xu; Qiang-min Xie; Rong-hua Zhang (Journal of Zhejiang University-SCIENCE B, 2013)

Association of single-nucleotide polymorphisms in the STAT3 gene with autoimmune thyroid disease in Chinese individuals - Ling Xiao; Fatuma-Said Muhali; Tian-tian Cai; Rong-hua Song; Renming Hu; Xiao-hong Shi; Wen-juan Jiang; Dan-Feng Li; Shuang-tao He; Jian Xu; Jin-an Zhang (Functional & Integrative Genomics, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Land use pattern, socio-economic development, and assessment of their impacts on ecosystem service value: study on natural wetlands distribution area (NWDA) in Fuzhou city, southeastern China - Yuan-Bin Cai; Hao Zhang; Wen-Bin Pan; Yan-Hong Chen; Xiang-Rong Wang (Environmental Monitoring and Assessment, 2013)

Cutaneous and Mucosal Phaeohyphomycosis Caused by Exophiala spinifera in a Pregnant Patient: Case Report and Literature Review - Le Wang; Xiaodong She; Guixia Lv; Yongnian Shen; Qing Cai; Rong Zeng; Caixia Li; Yiping Ge; Shuwen Deng; G. S. de Hoog; Min Li; Weida Liu (Mycopathologia, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Cloning and characterization of a thermostable carboxylesterase from inshore hot spring thermophile Geobacillus sp. ZH1 - Yanbing Zhu; Guangming Liu; Hebin Li; Jingwen Liu; Xiaoming Bai; Rong Guan; Huinong Cai (Acta Oceanologica Sinica, 2012)

Perifosine as potential anti-cancer agent inhibits proliferation, migration, and tube formation of human umbilical vein endothelial cells - Feng Ze Wang; Hong Rong Fei; Xiao Qian Li; Renjiu Shi; De Cai Wang (Molecular and Cellular Biochemistry, 2012)

Sixteen microsatellite markers developed from Bretschneidera sinensis (Bretschneideraceae) - Bi-Cai Guan; Guang-Rong Song; Gang Ge (Conservation Genetics Resources, 2012)

Structural determination of two new triterpenoid saponins acylated with monoterpenic acid from Gymnocladus chinensis Baill. - Wen Qi; Dan Yuan; Lian-Mei Yang; Ke-Hui Xie; Tian-Zhi Cai; Rong Yang; Hong-Zheng Fu (Natural Product Research, 2012)

Molecular characterization of the PpMADS1 gene from peach - Cui Li; Hua Xie; Lin Zhang; Yong Xu; Yun-Fu Li; Rong-Cai Ma (Tree Genetics & Genomes, 2012)

Nitrification activity and putative ammonia-oxidizing archaea in acidic red soils - Rong Huang; Yucheng Wu; Jinbo Zhang; Wenhui Zhong; Zhongjun Jia; Zucong Cai (Journal of Soils and Sediments, 2012)

HIV-infection resistance in PMBC-derived dendritic cells modified with recombinant virus - Cheng-lai Xia; Ping Zhu; Yan-tao Cai; Guang-bin Zhu; Zheng-rong Mei; Hanhui Huang; Di-xian Luo; Peng-ke Yan (Archives of Virology, 2012)

Adsorption of Pseudomonas putida on soil particle size fractions: effects of solution chemistry and organic matter - Huayong Wu; Daihua Jiang; Peng Cai; Xingmin Rong; Ke Dai; Wei Liang; Qiaoyun Huang (Journal of Soils and Sediments, 2012)

Synthesis of (–)-arctigenin derivatives and their anticancer activity - Chen Gui-Rong; Cai Li-Ping; Dou De-Qiang; Kang Ting-Guo; Li Hong-Fu; Li Fu-Rui; Jiang Ning (Natural Product Research, 2012)

Silicon-mediated amelioration of zinc toxicity in rice (Oryza sativa L.) seedlings - Hai-Hong Gu; Shu-Shun Zhan; Shi-Zhong Wang; Ye-Tao Tang; Rufus L. Chaney; Xiao-Hang Fang; Xin-De Cai; Rong-Liang Qiu (Plant and Soil, 2012)

Clinical outcomes of fertility-sparing treatments in young patients with epithelial ovarian carcinoma - Jun Hu; Li-rong Zhu; Zhi-qing Liang; Yuan-guang Meng; Hong-yan Guo; Peng-peng Qu; Cai-ling Ma; Cong-jian Xu; Bi-bo Yuan (Journal of Zhejiang University-SCIENCE B, 2011)

Multiallelic models of genetic effects and variance decomposition in non-equilibrium populations - José M. Álvarez-Castro; Rong-Cai Yang (Genetica, 2011)

Isolation and characterization of an AP2/ERF-RAV transcription factor BnaRAV-1-HY15 in Brassica napus L. HuYou15 - Jing Zhuang; Chao-Cai Sun; Xi-Rong Zhou; Ai-Sheng Xiong; Jian Zhang (Molecular Biology Reports, 2011)

A novel direct equipartition ray design (EquRay) procedure for toxicity interaction between ionic liquid and dichlorvos - Rong-Ni Dou; Shu-Shen Liu; Ling-Yun Mo; Hai-Ling Liu; Fu-Cai Deng (Environmental Science and Pollution Research, 2011)

Discovery and expression profile analysis of AP2/ERF family genes from Triticum aestivum - Jing Zhuang; Jian-Min Chen; Quan-Hong Yao; Fei Xiong; Chao-Cai Sun; Xi-Rong Zhou; Jian Zhang; Ai-Sheng Xiong (Molecular Biology Reports, 2011)

Exploitation of the late flowering species Brassica oleracea L. for the improvement of earliness in B. napus L.: an untraditional approach - M. Habibur Rahman; Rick A. Bennett; Rong-Cai Yang; Berisso Kebede; Mohan R. Thiagarajah (Euphytica, 2011)

Realized gains from selection for spring wheat grain yield are different in conventional and organically managed systems - Todd A. Reid; Rong-Cai Yang; Donald F. Salmon; Alireza Navabi; D. Spaner (Euphytica, 2011)

C/EBPε participates in all-trans retinoic acid induction of PI3Kγ in U937 cells via an intronic matrix attachment region sequence - Rong Cai; Xia Cai; Bin Chen; Weirong Xu; Jian Lu (Molecular Biology Reports, 2010)

Seismic analysis of the active character of the Taihang Mountain piedmont fault - Ming-Cai Xu; Jing-Hua Gao; Li-Xin Rong; Guang-Ke Wang; Xiao-Jiang Wang (Applied Geophysics, 2010)

Effects of immune activation on the retrieval of spatial memory - Zhen-Bo Huang; Hao Wang; Xiu-Rong Rao; Tao Liang; Jing Xu; Xiang-Sheng Cai; Guo-Qing Sheng (Neuroscience Bulletin, 2010)

SATB1 binds an intronic MAR sequence in human PI3kγ in vitro - Rong Cai; Weirong Xu; Bingbing Dai; Xia Cai; Rongting Xu; Jian Lu (Molecular Biology Reports, 2010)

Should spring wheat breeding for organically managed systems be conducted on organically managed land? - Todd A. Reid; Rong-Cai Yang; Donald F. Salmon; D. Spaner (Euphytica, 2009)

Preparation and In Vitro Evaluation of Solid Dispersions of Total Flavones of Hippophae rhamnoides L. - Yan Xie; Guowen Li; Xiurong Yuan; Zhenzhen Cai; Rong Rong (AAPS PharmSciTech, 2009)

Detection of plasmid-mediated IMP-1 metallo-β-lactamase and quinolone resistance determinants in an ertapenem-resistant Enterobacter cloacae isolate - Li-rong Chen; Hong-wei Zhou; Jia-chang Cai; Rong Zhang; Gong-xiang Chen (Journal of Zhejiang University-SCIENCE B, 2009)

Potential for seed-mediated gene flow in agroecosystems from transgenic safflower (Carthamus tinctorius L.) intended for plant molecular farming - Marc A. McPherson; Rong-Cai Yang; Allen G. Good; Ryan L. Nielson; Linda M. Hall (Transgenic Research, 2009)

Effects of different nitrogen forms on the growth and cytokinin content in xylem sap of tomato (Lycopersicon esculentum Mill.) seedlings - Ying Lin Lu; Yang Chun Xu; Qi Rong Shen; Cai Xia Dong (Plant and Soil, 2009)

Polycyclic Aromatic Hydrocarbons and Phthalic Acid Esters in Vegetables from Nine Farms of the Pearl River Delta, South China - Ce-Hui Mo; Quan-Ying Cai; Shi-Rong Tang; Qiao-Yun Zeng; Qi-Tang Wu (Archives of Environmental Contamination and Toxicology, 2009)

Expression analysis and genetic mapping of three SEPALLATA-like genes from peach (Prunus persica (L.) Batsch) - Yong Xu; Lin Zhang; Hua Xie; Yan-Qiu Zhang; M. Margarida Oliveira; Rong-Cai Ma (Tree Genetics & Genomes, 2008)

Molecular cloning, characterization and expression of atpA and atpB genes from Ginkgo biloba - Feng Xu; Rong Cai; Shui-yuan Cheng; Liu-ji Chen; Shu-han Cheng (Biologia, 2008)

Validating a segment on the short arm of chromosome 6 responsible for genetic variation in the hull silicon content and yield traits of rice - Wei-Min Dai; Ke-Qin Zhang; Ji-Rong Wu; Lei Wang; Bin-Wu Duan; Kang-Le Zheng; Run Cai; Jie-Yun Zhuang (Euphytica, 2008)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Bioenergetic Investigation of Action of Lithium to Tetrahymena thermophila bF5 by Microcalorimetry - Hui-Rong Li; Yi Liu; Cai-Qin Qin; Qiang-Guo Li (Biological Trace Element Research, 2007)

Synergistic induction of tumor cell death by combining cisplatin with an oncolytic adenovirus carrying TRAIL - Qiuwei Pan; Bisheng Liu; Jin Liu; Rong Cai; Yigang Wang; Cheng Qian (Molecular and Cellular Biochemistry, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

ARC contributes to the inhibitory effect of preconditioning on cardiomyocyte apoptosis - Yu Zhen Li; Xiu Hua Liu; Xiao Mei Zhu; Li Rong Cai (Apoptosis, 2007)

Genetic analysis of flowering and maturity time in high latitude spring wheat - Muhammad Iqbal; Alireza Navabi; Donald F. Salmon; Rong-Cai Yang; Brenda M. Murdoch; Steve S. Moore; Dean Spaner (Euphytica, 2007)

Crop yield, nitrogen uptake and nitrate-nitrogen accumulation in soil as affected by 23 annual applications of fertilizer and manure in the rainfed region of Northwestern China - Sheng-Mao Yang; S. S. Malhi; Jian-Rong Song; You-Cai Xiong; Wei-Yun Yue; Li Li Lu; Jian-Guo Wang; Tian-Wen Guo (Nutrient Cycling in Agroecosystems, 2006)

Detecting and estimating segregation distortion and linkage between glufosinate tolerance and blackleg resistance in Brassica napus L. - Rong-Cai Yang; Mohan R. Thiagarajah; Vipan K. Bansal; Gary R. Stringam; M. Habibur Rahman (Euphytica, 2006)

SSR allelic variation in almond (Prunus dulcis Mill.) - Hua Xie; Yi Sui; Feng-Qi Chang; Yong Xu; Rong-Cai Ma (Theoretical and Applied Genetics, 2006)

OsGLU1, A Putative Membrane-bound Endo-1,4-ß-D-glucanase from Rice, Affects Plant Internode Elongation - Hua-Lin Zhou; Si-Jie He; Yang-Rong Cao; Tao Chen; Bao-Xing Du; Cheng-Cai Chu; Jin-Song Zhang; Shou-Yi Chen (Plant Molecular Biology, 2006)

Evaluation of Aegilops tauschii Cosson for preharvest sprouting tolerance - Liu Deng-Cai; Lan Xiu-Jin; Wang Zhi-Rong; Zheng You-Liang; Zhou Yong-Hong; Yang Jun-Liang; Yen Chi (Genetic Resources and Crop Evolution, 1998)

Effects of fibroblast-mediated interleukin 3 and interleukin 6 gene therapy on hematopoiesis in mice treated with 5-fluorouracil - X. Cao; Dian Wen Ju; Rong Cai; Q. Tao; Yizhi Yu; Jianli Wang (Journal of Molecular Medicine, 1998)

Inheritance in synthetic hexaploid wheat ‘RSP’ of sprouting tolerance derived from Aegilops tauschii Cosson - Lan Xiu-Jin; Liu Deng-Cai; Wang Zhi-Rong (Euphytica, 1997)